Film, laminate, plasma processing apparatus, and method for manufacturing laminate

By using a film containing an adhesive resin and a thermally conductive filler, the problem of the existing adhesive member being reduced at extremely low temperatures is solved, and the effects of high adhesion and cold and hot cycle reliability are achieved.

CN119894987APending Publication Date: 2025-04-25TORAY INDUSTRIES INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380066626.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-21
Filing Date
2023-09-06
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The mechanical properties of the existing bonding members are reduced at extremely low temperatures below -30°C, resulting in problems such as decreasing adhesion, member peeling and cracks in the bonding members.

Method used

A film containing (SA) adhesive resin and (SD) thermal conductivity filler was used, and the shear strain of the film was 0.70-20 at -50°C, and the thermal conductivity at 25°C was 0.10-5.0W/(m·K), and a specific element content condition was met to improve the adhesion of the adhesive member and the reliability of the hot and cold cycle.

Benefits of technology

At extremely low temperatures around -50°C, the film can maintain high adhesion and cold and heat cycle reliability, avoiding component peeling and cracks from bonding components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894987A_ABST
    Figure CN119894987A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing a film which has excellent adhesion in which members are joined to each other even at extremely low temperatures of about-50 DEG C, and which has high thermal cycle reliability. The present invention is a film containing (SA) a binder resin and (SD) a thermally conductive filler, the (SD) thermally conductive filler including (SD1) a first thermally conductive filler and (SD2) a second thermally conductive filler, the (SD1) first thermally conductive filler having an average primary particle diameter of 1.0-200 [mu] m, the (SD2) second thermally conductive filler having an average primary particle diameter of 0.010 [mu] m or more but less than 1.0 [mu] m, and the film having a shear strain at-50 DEG C of 0.70-20,000 at-50 DEG C; and the thermal conductivity at 25 DEG C is 0.10-5.0 W / (m.K).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a film, a laminate, a plasma processing device, and a method for manufacturing the laminate. Background Art

[0002] In recent years, electronic terminal devices have been increasingly becoming more functional, miniaturized, thinner, and lighter. These electronic terminal devices are equipped with semiconductor devices, such as processors and memories. In the semiconductor manufacturing process, coating liquids such as adhesives and adhesive sheets are used for purposes such as bonding components to each other and temporarily holding components during the manufacturing process.

[0003] In addition, in the substrate processing device for performing sputtering, evaporation, chemical vapor deposition, ion implantation, etching, polishing, exposure or inspection in the semiconductor manufacturing process, an electrostatic chuck is used as a means of adsorbing and holding semiconductor wafers, glass substrates, etc. For example, in a plasma processing device, a mounting table for placing a semiconductor wafer is provided inside a vacuum chamber, and the mounting table is mainly composed of an electrostatic chuck and a cooler for controlling the temperature of the electrostatic chuck. The electrostatic chuck is made by sandwiching an electrode between ceramic dielectric components and firing them, and has a base component, a ceramic dielectric component formed of ceramic, and a bonding component for bonding the base component to the ceramic dielectric component. The electrostatic chuck is a holding device that uses the electrostatic attraction generated by applying a voltage to the built-in electrode to adsorb and hold the semiconductor wafer, etc. on the surface of the ceramic dielectric component.

[0004] On the other hand, in the manufacture of semiconductor devices, in order to achieve high density / high integration of 3D-NAND memories, etc., high aspect ratio etching processing with large etching depth is required. In order to increase the aspect ratio in the etching process and reduce the process time, a method of etching at an extremely low temperature below -30°C can be cited (for example, refer to Patent Document 1). Therefore, an adhesive component that can be used even at an extremely low temperature below -30°C is required. An adhesive component that can be used even at such an extremely low temperature is considered necessary in other holding devices such as vacuum chucks in addition to electrostatic chucks.

[0005] Examples of the adhesive member in an electrostatic chuck and the like include silicone resin-based adhesive members and acrylic resin-based adhesive members (for example, refer to Patent Document 2 or Patent Document 3).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent No. 6621882

[0009] Patent Document 2: Japanese Patent Application Publication No. 2011-151280

[0010] Patent Document 3: Japanese Patent Application Publication No. 2014-207374 Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, the adhesive components described in Patent Document 2 or Patent Document 3 have problems such as peeling of components and cracking of adhesive components due to reduced adhesion of components to each other, since their mechanical properties are reduced at extremely low temperatures below -30°C. The present invention aims to provide a film having excellent adhesion of components to each other even at extremely low temperatures of about -50°C and high thermal cycle reliability.

[0013] Means for solving problems

[0014] In order to solve the above problems, the film of the present invention has the following structures [1] to

[20] .

[0015] [1] A film comprising (SA) a binder resin and (SD) a thermally conductive filler,

[0016] The (SD) thermally conductive filler includes (SD1) a first thermally conductive filler and (SD2) a second thermally conductive filler.

[0017] The average primary particle size of the first thermally conductive filler (SD1) is 1.0 to 200 μm,

[0018] The average primary particle size of the second thermally conductive filler (SD2) is 0.010 μm or more and less than 1.0 μm,

[0019] The shear strain of the film at -50°C is 0.70 to 20,

[0020] The thermal conductivity of the film at 25° C. is 0.10 to 5.0 W / (m·K).

[0021] [2] The film according to [1] above, wherein the elastic modulus at -50°C is 0.10 to 200 MPa.

[0022] [3] The film according to [1] or [2] above, which satisfies at least one of the following conditions (S1a), (S2a), (S3a), (S1b), (S2b) and (S3b).

[0023] (S1a) The boron content in the film is 5.0 mass % or less

[0024] (S2a) The phosphorus content in the film is 1,000 mass ppm or less

[0025] (S3a) The total content of chlorine and bromine in the film is 1,000 mass ppm or less

[0026] (S1b) The total content of ions containing the boron element in the film is 5.0 mass % or less

[0027] (S2b) The total content of ions containing phosphorus in the film is 5,000 mass ppm or less

[0028] (S3b) The total content of chloride ions and bromide ions in the film is 1,000 mass ppm or less.

[0029] [4] The film according to any one of [1] to [3] above, which satisfies at least one of the following conditions (S4a) and (S4b).

[0030] (S4a) The content of platinum in the film is 1,000 mass ppm or less

[0031] (S4b) The total content of ions containing the platinum element in the film is 5,000 mass ppm or less.

[0032] [5] The film according to any one of [1] to [4] above, which satisfies at least one of the following conditions (S5a) and (S5b).

[0033] (S5a) The total content of the organosilane compound having 1 to 2 silicon atoms in the film is 1,000 mass ppm or less. (S5b) The total content of the cyclic organosilicon compound in the film is 1,000 mass ppm or less.

[0034] [6] A film comprising (SA) a binder resin and (SD) a thermally conductive filler,

[0035] The elastic modulus of the film at -50°C is 0.10 to 200 MPa,

[0036] The thermal conductivity of the film at 25° C. is 0.10 to 5.0 W / (m·K).

[0037] [7] The film according to [6] above, wherein the shear strain at -50°C is 0.70 to 20.

[0038] [8] The film according to [6] or [7] above, which satisfies at least one of the following conditions (S1a), (S2a), (S3a), (S1b), (S2b) and (S3b).

[0039] (S1a) The boron content in the film is 5.0 mass % or less

[0040] (S2a) The phosphorus content in the film is 1,000 mass ppm or less

[0041] (S3a) The total content of chlorine and bromine in the film is 1,000 mass ppm or less

[0042] (S1b) The total content of ions containing the boron element in the film is 5.0 mass % or less

[0043] (S2b) The total content of ions containing phosphorus in the film is 5,000 mass ppm or less

[0044] (S3b) The total content of chloride ions and bromide ions in the film is 1,000 mass ppm or less.

[0045] [9] The film according to any one of [6] to [8] above, which satisfies at least one of the following conditions (S4a) and (S4b).

[0046] (S4a) The content of platinum in the film is 1,000 mass ppm or less

[0047] (S4b) The total content of ions containing the platinum element in the film is 5,000 mass ppm or less.

[0048]

[10] The film according to any one of [6] to [9] above, which satisfies at least one of the following conditions (S5a) and (S5b).

[0049] (S5a) The total content of the organosilane compound having 1 to 2 silicon atoms in the film is 1,000 mass ppm or less. (S5b) The total content of the cyclic organosilicon compound in the film is 1,000 mass ppm or less.

[0050]

[11] The film according to any one of [1] to

[10] above, wherein the binder resin (SA) comprises (SA1) a resin having a silicone structure and / or a siloxane structure in a structural unit of the resin.

[0051]

[12] The film according to

[11] above, wherein the content ratio of the aliphatic group in the total of the aliphatic group and the aromatic group bonded to the silicon atom in the above-mentioned organic silicon structure and / or the above-mentioned siloxane structure is 80 to 100 mol%.

[0052]

[13] The film according to

[11] or

[12] , wherein the resin (SA1) containing a silicone structure and / or a siloxane structure in the structural unit of the resin contains (SA1-1) containing a resin selected from the group consisting of an imide structure, an amide structure and More than one resin in the azole structure.

[0053]

[14] The film according to

[13] , wherein the resin structural unit of the above (SA1-1) comprises an imide structure, an amide structure and One or more resins in the azole structure have one or more residues selected from the following (1) and (2).

[0054] (1) A diamine residue, a diamine derivative residue, a bisaminophenol compound residue, or a bisaminophenol compound derivative residue containing an organic silicon structure and / or a siloxane structure

[0055] (2) A tetracarboxylic acid residue, a tetracarboxylic acid derivative residue, a tricarboxylic acid residue, a tricarboxylic acid derivative residue, a dicarboxylic acid residue or a dicarboxylic acid derivative residue containing an organosilicon structure and / or a siloxane structure.

[0056]

[15] The film according to any one of [1] to

[14] above, comprising (SB) an epoxy compound or a compound having a structure derived from an epoxy compound (hereinafter, “(SB) compound”),

[0057] The (SB) compound contains one or more selected from (SB1) a compound having a structure containing an oxyalkylene group, (SB2) a compound having a structure containing at least two aromatic structures and having a structure containing an oxyalkylene group, and (SB3) a compound having a tertiary amine structure bonded to an arylene group and two divalent organic groups.

[0058]

[16] The film according to any one of [1] to

[15] above, comprising (SC) an amine compound or a compound having a structure derived from an amine compound (hereinafter, “(SC) compound”),

[0059] The (SC) compound contains (SC1) a compound having an organosilicon structure and / or a siloxane structure and having at least two alkylene groups bonded to a silicon atom in the organosilicon structure and / or the siloxane structure.

[0060]

[17] The film according to any one of [1] to

[16] above, wherein the elastic modulus of the film at 25°C is 0.010 to 1.0 MPa.

[0061]

[18] The film according to any one of [1] to

[16] above, wherein the film is a cured product of the composition.

[0062]

[19] The film according to any one of [1] to

[18] above, which is used for an electrostatic chuck.

[0063]

[20] A laminate comprising, in this order, a base member, the film according to any one of [1] to

[19] , and a ceramic dielectric member,

[0064] The base member and the ceramic dielectric member have different thermal expansion coefficients.

[0065]

[21] The laminate according to

[20] above, wherein the difference in thermal expansion coefficient between the base member and the ceramic dielectric member is 1.0 to 30 ppm / K.

[0066]

[22] A plasma processing device comprising a plasma generation source and the laminated body described in

[20] or

[21] above.

[0067]

[23] A method for producing a laminate, comprising the steps of disposing a base member, disposing the film according to any one of [1] to

[19] above, and disposing a ceramic dielectric member.

[0068] Effects of the Invention

[0069] According to the present invention, it is possible to provide a film having excellent adhesion to members even at an extremely low temperature of about -50°C and high thermal cycle reliability. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 It is a schematic cross-sectional view showing Embodiment 1 of a laminated body which is a laminated body having a first support, a film, and a second support.

[0071] Figure 2 Schematic cross-sectional view showing Embodiment 2 of a laminated body which is a laminated body including a base member, a film, and a ceramic dielectric member. DETAILED DESCRIPTION

[0072] Hereinafter, the film of the present invention will be described. It should be noted that, when described as the film of the present invention, it is a common description of the first and second schemes of the film of the present invention. On the other hand, when describing a film of a specific scheme, it is recorded as the first scheme of the film of the present invention, etc. However, the present invention is not limited to the following embodiments, and various changes can be made within the scope of being able to achieve the purpose of the invention and not exceeding the main purpose of the invention.

[0073] It should be noted that the main chain of the resin refers to the longest chain among the chains constituting the resin containing the structural unit. The side chain of the resin refers to a chain that is branched from the main chain or combined with the main chain among the chains constituting the resin containing the structural unit and has a shorter chain length than the main chain. The terminal of the resin refers to a structure that closes the main chain, for example, a structure derived from an end-capping agent, etc.

[0074] In this specification, the term "overlapping" means directly or indirectly stacking with respect to the z-axis direction. That is, when a certain layer overlaps with another layer, these layers may be in contact with each other, or another layer may exist between these layers.

[0075] In this specification, the so-called organic silicon structure refers to a structure with Si-O-Si bonds as the main skeleton and two organic groups on the silicon atom. That is, the silicon atom in the organic silicon structure is bonded to two organic groups and two oxygen atoms. In addition, the so-called siloxane structure refers to a structure with Si-O-Si bonds as the main skeleton and one organic group on the silicon atom. That is, the silicon atom in the siloxane structure is bonded to one organic group and three oxygen atoms.

[0076] <Film>

[0077] A first embodiment of the film of the present invention is a film comprising (SA) a binder resin and (SD) a thermally conductive filler.

[0078] The (SD) thermally conductive filler includes (SD1) a first thermally conductive filler and (SD2) a second thermally conductive filler, wherein the average primary particle size of the (SD1) first thermally conductive filler is 1.0 to 200 μm, the average primary particle size of the (SD2) second thermally conductive filler is 0.010 μm or more and less than 1.0 μm, the shear strain of the film at -50°C is 0.70 to 20, and the thermal conductivity at 25°C is 0.10 to 5.0 W / (m·K). By having the above-mentioned structure, the present invention can provide a film having excellent adhesion of components joined to each other even at an extremely low temperature of about -50°C and high thermal cycle reliability. It can be considered that this is because the anchoring effect brought about by the combined use of fillers with a specific average primary particle size reduces the slope of the stress-strain curve in which the vertical axis is set to stress and the horizontal axis is set to strain (increase in strain per unit stress), so that the shear strain at -50°C can be adjusted to a specific range. Therefore, it is estimated that the high shear strain at an extremely low temperature of about -50°C provides flexibility capable of relaxing the difference in thermal expansion coefficient between members to which the film is bonded, and the followability to each member is improved, thereby improving the adhesion and thermal cycle reliability.

[0079] It is also believed that the film contains two types of thermally conductive fillers with a specific average primary particle size, so that the heat generated in the joined components can be efficiently dissipated, and the internal stress caused by the temperature rise of the components can be reduced. In addition, it is also presumed that the heat accumulated in the film can be reduced, and the change in mechanical properties caused by the temperature rise of the film can be suppressed.

[0080] It is also believed that the heat generated in the joined components can be efficiently dissipated by increasing the thermal conductivity of the film, and the internal stress caused by the temperature rise of the components can be reduced. In addition, it is also presumed that the heat accumulated in the film can be reduced, and the change in mechanical properties caused by the temperature rise of the film can be suppressed.

[0081] The so-called film refers to a film that can form a self-supporting film as a single film. The film is preferably adhesive, and it is also preferred to join multiple components. The so-called being able to form a self-supporting film as a single film means that a film with a width of more than 5.0 cm, a length of more than 5.0 cm, and a thickness of more than 5.0 μm can be formed without a support.

[0082] A second embodiment of the film of the present invention is a film comprising (SA) a binder resin and (SD) a thermally conductive filler, wherein the elastic modulus at -50°C is 0.10 to 200 MPa and the thermal conductivity at 25°C is 0.10 to 5.0 W / (m·K).

[0083] By adopting the above-mentioned structure, the present invention can provide a film having excellent adhesion to components even at an extremely low temperature of about -50°C and high thermal cycle reliability. It is presumed that this is because the low elastic modulus at an extremely low temperature of about -50°C can reduce the internal stress caused by the difference in thermal expansion coefficient between the components to which the film is bonded, improve the followability to each component, and thus improve the adhesion and thermal cycle reliability.

[0084] It is also believed that the reason is that the high thermal conductivity of the film can effectively dissipate the heat generated in the components to be joined, and the internal stress caused by the temperature rise of the components can be reduced. In addition, it is also speculated that the heat accumulated in the film can be reduced, and the change of mechanical properties caused by the temperature rise of the film can be suppressed.

[0085] <(SA) Binder resin>

[0086] The film of the present invention contains a (SA) binder resin. The so-called (SA) binder resin is a heat-resistant resin that at least partially remains in a cured product obtained by curing the composition used to form the film of the present invention. The (SA) binder resin is preferably a resin that can form a cross-linked structure with the (SB) compound described later or a resin that has formed a cross-linked structure. The cross-linked structure is preferably formed by reaction, and can be formed by heating, formed by irradiation with energy rays, etc., without particular limitation.

[0087] The (SA) binder resin preferably has an acidic group or a structure derived from an acidic group, and more preferably has an acidic group or a structure derived from an acidic group in the repeating unit of the resin. The above-mentioned acidic group is preferably a phenolic hydroxyl group, a hydroxyimide group, a hydroxyamide group, a silanol group, a 1,1-bis(trifluoromethyl)hydroxymethyl group, a mercapto group, a carboxyl group, a carboxylic acid anhydride group or a sulfonic acid group, and more preferably a phenolic hydroxyl group, a carboxyl group or a carboxylic acid anhydride group. It should be noted that when the (SA) binder resin satisfies the conditions of (P1a) and / or (P2a) described below, or when the film of the present invention satisfies at least one of the conditions of (S3α) and (S3β) described below, the above-mentioned acidic group is preferably a phenolic hydroxyl group, a hydroxyimide group, a hydroxyamide group, a silanol group, a mercapto group, a carboxyl group, a carboxylic acid anhydride group or a sulfonic acid group.

[0088] From the viewpoint of improving adhesion and improving thermal cycle reliability, the acid equivalent of the (SA) binder resin is preferably 200 g / mol or more, more preferably 250 g / mol or more, and further preferably 300 g / mol or more. On the other hand, from the viewpoint of improving thermal cycle reliability, the acid equivalent of the (SA) binder resin is preferably 600 g / mol or less, more preferably 500 g / mol or less, and further preferably 450 g / mol or less.

[0089] The above-mentioned (SA) binder resin having an acidic group or a structure derived from an acidic group is suitable for adjusting the shear strain at -50°C to within the range of 0.70 to 20 and / or adjusting the elastic modulus at -50°C to within the range of 0.10 to 200 MPa by forming a cross-linked structure with the (SB) compound described later. In addition, the above-mentioned acidic group or the structure derived from the acidic group can improve the dispersibility of the filler through interaction with the (SD) thermally conductive filler described later, and the effect of improving the thermal conductivity of the film becomes significant. It is inferred that since the followability to each component is improved, the adhesion and cold and hot cycle reliability are improved.

[0090] <(SA1) Resin>

[0091] From the perspective of improving adhesion at extremely low temperatures of around -50°C and improving thermal cycle reliability, the (SA) binder resin preferably contains (SA1) a resin containing a silicone structure and / or a siloxane structure in the structural unit of the resin (hereinafter, "(SA1) resin").

[0092] The organosilicon structure and siloxane structure of the (SA1) resin are preferably bonded to at least two alkylene groups, and are structures having a valency of 2 or more through these alkylene groups. The above-mentioned structures having a valency of 2 or more are more preferably 3 or more, and further preferably 4 or more. On the other hand, the above-mentioned structures having a valency of 2 or more are preferably 6 or less.

[0093] The number of silicon atoms in the organic silicon structure and / or siloxane structure in the (SA1) resin is preferably 5 or more, more preferably 10 or more, further preferably 15 or more, and particularly preferably 20 or more. On the other hand, the number of silicon atoms is preferably 30 or less, more preferably 27 or less, and further preferably 25 or less.

[0094] In the resin (SA1), the organosilicon structure is preferably a dialkyl organosilicon structure and / or a monoalkyl organosilicon structure, and the siloxane structure is preferably a monoalkylsiloxane structure.

[0095] The number of carbon atoms in the alkyl group of the dialkyl organosilicon structure and the monoalkyl organosilicon structure is preferably 1 or more, more preferably 2 or more, and even more preferably 3 or more. On the other hand, the number of carbon atoms in the alkyl group is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less.

[0096] The number of carbon atoms in the alkyl group of the monoalkylsiloxane structure is preferably 1 or more, more preferably 2 or more, and even more preferably 3 or more. On the other hand, the number of carbon atoms in the alkyl group is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less.

[0097] From the viewpoint of improving adhesion and improving thermal cycle reliability, in the resin (SA1), the content ratio of the aliphatic group in the total of the aliphatic group and the aromatic group bonded to the silicon atom in the silicone structure and / or the siloxane structure is preferably 80 mol% or more, more preferably 85 mol% or more, and further preferably 90 mol% or more. On the other hand, from the viewpoint of improving thermal cycle reliability, the content ratio of the aliphatic group in the total of the aliphatic group and the aromatic group is preferably 100 mol% or less, more preferably 99 mol% or less, and further preferably 97 mol% or less.

[0098] The aliphatic group possessed by the (SA1) resin is preferably an alkyl group. The preferred carbon number of the alkyl group is also the same as described above. The alkyl group is preferably a methyl group, an ethyl group, a propyl group, a butyl group or a hexyl group. The carbon number of the aromatic group possessed by the (SA1) resin is preferably 6 or more, more preferably 7 or more, and further preferably 8 or more. On the other hand, the carbon number of the aromatic group is preferably 15 or less, more preferably 12 or less, and further preferably 10 or less. The aromatic group is preferably a phenyl group, a tolyl group, a xylyl group, a phenoxy group, a tolyloxy group or a xylyloxy group.

[0099] The above-mentioned resin (SA1) is suitable in that the shear strain at -50°C is adjusted to within the range of 0.70 to 20 and / or the elastic modulus at -50°C is adjusted to within the range of 0.10 to 200 MPa due to the flexible skeleton derived from the silicone structure or the siloxane structure.

[0100] <(SA1-1) Resin>

[0101] From the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving the thermal cycle reliability, the resin (SA1) preferably contains (SA1-1) a structural unit of the resin containing an imide structure, an amide structure and One or more resins having an azole structure are "hereinafter, (SA1-1) resins".

[0102] (SA1-1) resin is polyimide, polybenzo The oxazoles, their precursors, and copolymers formed from two or more of them contain, in the structural unit of the resin, a structure selected from an imide structure, an amide structure, and More than one resin in the azole structure.

[0103] From the viewpoint of improving adhesion and thermal cycle reliability, the resin (SA1-1) preferably contains a polyimide, a polyimide precursor, a polybenzoic acid, Azoles, polybenzo One or more of azole precursors, polyamideimide, polyamideimide precursors, polyamide, and copolymers of two or more thereof (hereinafter, "polyimide-based resins"). The (SA1-1) resin may be a single resin or a copolymer thereof.

[0104] The resin (SA1-1) preferably has one or more residues selected from the following (1) and (2).

[0105] (1) A diamine residue, a diamine derivative residue, a bisaminophenol compound residue, or a bisaminophenol compound derivative residue containing an organic silicon structure and / or a siloxane structure

[0106] (2) A tetracarboxylic acid residue, a tetracarboxylic acid derivative residue, a tricarboxylic acid residue, a tricarboxylic acid derivative residue, a dicarboxylic acid residue or a dicarboxylic acid derivative residue containing an organosilicon structure and / or a siloxane structure.

[0107] The residue of the above-mentioned (1) possessed by the (SA1-1) resin is a diamine residue containing an organic silicon structure and / or a siloxane structure, a diamine derivative residue containing an organic silicon structure and / or a siloxane structure, a bisaminophenol compound residue containing an organic silicon structure and / or a siloxane structure, or a bisaminophenol compound derivative residue containing an organic silicon structure and / or a siloxane structure.

[0108] The residue of the above-mentioned (2) possessed by the (SA1-1) resin is (2) a tetracarboxylic acid residue containing an organic silicon structure and / or a siloxane structure, a tetracarboxylic acid derivative residue containing an organic silicon structure and / or a siloxane structure, a tricarboxylic acid residue containing an organic silicon structure and / or a siloxane structure, a tricarboxylic acid derivative residue containing an organic silicon structure and / or a siloxane structure, a dicarboxylic acid residue containing an organic silicon structure and / or a siloxane structure, or a dicarboxylic acid derivative residue containing an organic silicon structure and / or a siloxane structure.

[0109] The residue of the above-mentioned (1) possessed by the resin (SA1-1) is divalent or more, preferably trivalent or more. On the other hand, the residue of the above-mentioned (1) is preferably hexavalent or less, more preferably tetravalent or less. In addition, the residue of the above-mentioned (2) possessed by the resin (SA1-1) is divalent or more, preferably trivalent or more, more preferably tetravalent or more. On the other hand, the residue of the above-mentioned (2) is preferably hexavalent or less.

[0110] The residue of the above (2) possessed by the (SA1-1) resin is preferably a tetracarboxylic dianhydride residue, a tricarboxylic anhydride residue or a dicarboxylic anhydride residue containing an organic silicon structure and / or a siloxane structure. In addition, the residue of the above (2) preferably has an anhydride residue containing a phthalic acid structure, an anhydride residue containing a succinic acid structure or an anhydride residue containing a maleic acid structure.

[0111] From the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving the thermal cycle reliability, in the resin (SA1-1), the total content ratio of the residues of the above-mentioned (1) and the residues of the above-mentioned (2) in the total of all amine residues and all carboxylic acid residues is preferably 10 mol% or more, more preferably 30 mol% or more, further preferably 40 mol% or more, further preferably 60 mol% or more, and particularly preferably 80 mol% or more. On the other hand, from the viewpoint of improving the thermal cycle reliability, the total content ratio of the residues of the above-mentioned (1) and the residues of the above-mentioned (2) in the total of all amine residues and all carboxylic acid residues is preferably 100 mol% or less, more preferably 99 mol% or less, and further preferably 97 mol% or less.

[0112] From the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving the thermal cycle reliability, in the resin (SA1-1), the total content ratio of the residues of the above-mentioned (1) in all the amine residues is preferably 10 mol% or more, more preferably 30 mol% or more, further preferably 40 mol% or more, further preferably 60 mol% or more, and particularly preferably 80 mol% or more. On the other hand, from the viewpoint of improving the thermal cycle reliability, the total content ratio of the residues of the above-mentioned (1) in all the amine residues is preferably 100 mol% or less, more preferably 99 mol% or less, and further preferably 97 mol% or less.

[0113] From the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving the thermal cycle reliability, in the (SA1-1) resin, the total content ratio of the residues of the above-mentioned (2) in all the carboxylic acid residues is preferably 10 mol% or more, more preferably 30 mol% or more, further preferably 40 mol% or more, further preferably 60 mol% or more, and particularly preferably 80 mol% or more. On the other hand, from the viewpoint of improving the thermal cycle reliability, the total content ratio of the residues of the above-mentioned (2) in all the carboxylic acid residues is preferably 100 mol% or less, more preferably 99 mol% or less, and further preferably 97 mol% or less.

[0114] The residue of (1) in the resin (SA1-1) preferably has a structure represented by the general formula (11). The residue of (2) in the resin (SA1-1) preferably has a structure represented by the general formula (12).

[0115]

[0116] In the general formula (11) and the general formula (12), X 1 ~X 4 Each of Y independently represents a direct bond, an oxygen atom, an alkylene group having 1 to 30 carbon atoms, an alkyleneoxy group having 1 to 30 carbon atoms, or an arylene group having 6 to 30 carbon atoms. 1 and Y 2 Each independently represents a trivalent organic group having 1 to 20 carbon atoms. 21 ~R 32 Each independently represents an alkyl group having 1 to 30 carbon atoms, an aryl group having 6 to 30 carbon atoms, or an aryloxy group having 6 to 30 carbon atoms. x and y each independently represent an integer of 1 to 100.* 1 ~* 8 Each independently represents a bonding point to other structures.

[0117] In the general formula (11) and the general formula (12), the trivalent organic group having 1 to 20 carbon atoms is preferably a trivalent hydrocarbon group having 1 to 20 carbon atoms. The alkyl group having 1 to 30 carbon atoms is preferably a methyl group, an ethyl group, a propyl group, a butyl group or a hexyl group. The aryl group having 6 to 30 carbon atoms is preferably a phenyl group, a tolyl group or a xylyl group. The aryloxy group having 6 to 30 carbon atoms is preferably a phenoxy group, a tolyloxy group or a xylyloxy group. The alkylene group having 1 to 30 carbon atoms is preferably a methylene group, an ethylene group, a propylene group, a butylene group or a hexylene group. The arylene group having 6 to 30 carbon atoms is preferably a phenylene group, a tolylene group or a xylylene group. It should be noted that the alkyl group and the alkylene group have a straight chain structure or a branched structure. The above-mentioned alkyl group, aryl group, aryloxy group, alkylene group and arylene group may have a heteroatom and may be any of an unsubstituted body or a substituted body.

[0118] From the viewpoint of improving the adhesion at an extremely low temperature of about -50°C and improving the thermal cycle reliability, x is preferably 6 or more, more preferably 15 or more, further preferably 24 or more, further preferably 28 or more, and particularly preferably 32 or more. On the other hand, from the viewpoint of improving the adhesion at an extremely low temperature of about -50°C and improving the thermal cycle reliability, x is preferably 100 or less, more preferably 70 or less, further preferably 50 or less, and particularly preferably 44 or less.

[0119] From the viewpoint of improving the adhesion at an extremely low temperature of about -50°C and improving the thermal cycle reliability, y is preferably 6 or more, more preferably 11 or more, further preferably 15 or more, and particularly preferably 18 or more. On the other hand, from the viewpoint of improving the adhesion at an extremely low temperature of about -50°C and improving the thermal cycle reliability, y is preferably 100 or less, more preferably 50 or less, further preferably 30 or less, and particularly preferably 26 or less.

[0120] From the viewpoint of the effect of the above invention, in the (SA1-1) resin, the total content ratio of the structure represented by the general formula (11) in the residue of the above (1) in which x is 6 or more and 100 or less is preferably 50 mol% or more, more preferably 70 mol% or more, and further preferably 90 mol% or more. On the other hand, from the viewpoint of the effect of the above invention, the total content ratio of the structure represented by the general formula (11) in which x is 6 or more and 100 or less is preferably 100 mol% or less, more preferably 99 mol% or less, and further preferably 97 mol% or less.

[0121] From the viewpoint of the effect of the above invention, in the (SA1-1) resin, the total content ratio of the structure represented by the general formula (12) in the residue of the above (2) in which y is 6 or more and 100 or less is preferably 50 mol% or more, more preferably 70 mol% or more, and further preferably 90 mol% or more. On the other hand, from the viewpoint of the effect of the above invention, the total content ratio of the structure represented by the general formula (12) in which y is 6 or more and 100 or less is preferably 100 mol% or less, more preferably 99 mol% or less, and further preferably 97 mol% or less.

[0122] The above-mentioned resin (SA1-1) has a soft skeleton derived from an organic silicon structure or a siloxane structure and a polyimide structure, an amide structure or a polyimide structure. The mechanical properties of the resin (SA1-1) are improved by the azole structure, thereby adjusting the shear strain at -50°C to within the range of 0.70 to 20 and / or adjusting the elastic modulus at -50°C to within the range of 0.10 to 200 MPa. The coordination ability of the azole structure to each component makes it act as an anchor at the interface with the component at extremely low temperatures. Therefore, it is estimated that the followability to each component is improved, and the adhesion and thermal cycle reliability are improved.

[0123] Examples of the amine monomer for introducing the residue of (1) into the (SA1-1) resin include X-22-161A (amino equivalent: 800 g / mol), X-22-161B (amino equivalent: 1,500 g / mol), KF-8012 (amino equivalent: 2,200 g / mol), KF-8010 (amino equivalent: 430 g / mol) or KF-8008 (amino equivalent: 5,700 g / mol) (all manufactured by Shin-Etsu Chemical Co., Ltd.) which are dimethyl silicones modified with amino groups at both ends; or X-22-1660B-3 (amino equivalent: 2,200 g / mol) or X-22-9409 (amino equivalent: 650 g / mol) (all manufactured by Shin-Etsu Chemical Co., Ltd.) which are methylphenyl silicones modified with amino groups at both ends.

[0124] Examples of the acid monomer used to introduce the residue of (2) into the (SA1-1) resin include X-22-168AS (anhydride group equivalent: 500 g / mol), X-22-168A (anhydride group equivalent: 1,000 g / mol), X-22-168B (anhydride group equivalent: 1,600 g / mol) or X-22-168-P5-B (anhydride group equivalent: 2,100 g / mol) (all manufactured by Shin-Etsu Chemical Co., Ltd.).

[0125] The resin (SA1-1) preferably has a residue having an acidic group or a residue having a structure derived from an acidic group, and more preferably has a residue having an acidic group or a residue having a structure derived from an acidic group in a repeating unit of the resin. Examples of amine monomers or acid monomers for introducing such residues into the (SA1-1) resin include bis(3-amino-4-hydroxyphenyl)methane, 1,1-bis(3-amino-4-hydroxyphenyl)ethane, 2,2-bis(3-amino-4-hydroxyphenyl)propane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, bis(3-amino-4-hydroxyphenyl)sulfone, bis[4-(4-aminophenoxy)phenyl]ether, bis(3-amino-4-hydroxyphenyl)ether, 9,9-bis(3-amino-4-hydroxyphenyl)fluorene, N,N'-bis[5,5'-hexafluoropropane-2,2-diyl-bis(2-hydroxyphenyl)]bis(3-aminobenzoic acid amide) or N,N'-bis[5,5'-hexafluoropropane-2,2-diyl-bis(2-hydroxyphenyl)]bis(3,4-dicarboxybenzoic acid amide).

[0126] <Polyimide-based resin>

[0127] Examples of the polyimide precursor include polyamic acid, polyamic acid ester, polyamic acid amide, and polyisoimide. Examples of the polyimide include resins obtained by subjecting a polyimide precursor to dehydration ring closure by heating or a reaction using a catalyst.

[0128] As polyphenylene As the azole precursor, for example, polyhydroxyamide can be mentioned. Azoles, for example, can be obtained by making polybenzoic acid The resin is obtained by dehydration ring closure of an azole precursor by heating or a reaction using a catalyst.

[0129] Examples of the polyamideimide precursor include resins obtained by reacting tricarboxylic anhydride and diamine, etc. Examples of the polyamideimide include resins obtained by subjecting a polyamideimide precursor to dehydration ring closure by heating or a reaction using a catalyst.

[0130] Examples of polyamides include resins obtained by reacting dicarboxylic acids or corresponding dicarboxylic acid active diesters with diamines or diisocyanate compounds. Azoles, polybenzo The azole precursor, polyamideimide and polyamideimide precursor may be a copolymer with polyamide.

[0131] The polyimide resin may have a structure blocked by a monoamine, a dicarboxylic anhydride or a monocarboxylic acid derivative at the end of the resin. From the viewpoint of improving adhesion and improving thermal cycle reliability, the polyimide resin preferably has a crosslinking group or a free radical polymerizable group capable of reacting with the resin, etc. at the end of the resin, and more preferably has a maleimide group or a nadimide group.

[0132] <(SA) Content of fluorine element in the structure of the binder resin>

[0133] From the viewpoint of improving the adhesion at extremely low temperatures of around -50°C and improving the thermal cycle reliability, the (SA) binder resin also preferably satisfies the following condition (P1a). The (SA) binder resin more preferably further satisfies the following condition (P2a). When the (SA) binder resin is a polyimide-based resin, from the same viewpoint, it is also preferred to satisfy the following condition (P1a), and more preferably further satisfy the following condition (P2a). It should be noted that when the (SA) binder resin satisfies the following condition (P2a), the following condition (P1a) is satisfied by the fluorine ions in the structure of the (SA) binder resin.

[0134] (P1a)(SA) The content of fluorine element in the structure of the binder resin is 10,000 ppm by mass or less

[0135] (P2a) The content of fluorine ions in the structure of the (SA) binder resin is 10,000 ppm by mass or less.

[0136] From the viewpoint of the effect of the above invention, the content of fluorine element in the structure of the (SA) binder resin is preferably more than 0.000 mass ppm, more preferably 0.010 mass ppm or more, further preferably 0.030 mass ppm or more, further preferably 0.050 mass ppm or more, particularly preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, from the viewpoint of the effect of the above invention, the content of fluorine element is preferably 10,000 mass ppm or less, more preferably 5,000 mass ppm or less, further preferably 1,000 mass ppm or less, further preferably 500 mass ppm or less, further preferably 300 mass ppm or less, further preferably 100 mass ppm or less, further preferably 50 mass ppm or less, further preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further preferably 5 mass ppm or less, particularly preferably 3 mass ppm or less, and particularly preferably 1 mass ppm or less.

[0137] It is considered that fluorine element has a large number of unshared electron pairs, and by including fluorine element in the structure of the (SA) binder resin, electron donation of these electron pairs is utilized to facilitate the formation of coordination bonds with the surface of the member.

[0138] The preferred range of the content of fluorine ions in the structure of the (SA) binder resin is also the same as the preferred range of the content of fluorine elements in the structure of the (SA) binder resin described above with respect to the upper limit and the lower limit, respectively.

[0139] The content of fluorine element in the structure of the (SA) binder resin may be 0.000 mass ppm. The content of fluorine ion in the structure of the (SA) binder resin may be 0.000 mass ppm.

[0140] It is speculated that by making the film contain a (SA) binder resin with a content of fluorine element below a specific value, the content of fluorine element, fluorine ion or anion containing fluorine element derived from these resins in these resins becomes below a specific value, so that the local interaction with the surface of the member to be joined is improved by the hydrogen bond of each component in the film, the electronegativity of fluorine atoms, etc. In addition, it can be considered that by intentionally making the content of the above-mentioned components below a specific value, the polarization structure and charge balance in the film are controlled, and the influence of ionic components, etc. that have an adverse effect on the mechanical properties of the film in the hot and cold cycle can be suppressed. It is speculated that through these effects, it acts as an anchor in the interface with the member at extremely low temperatures, so that the followability of each member is improved, and the adhesion and hot and cold cycle reliability are improved.

[0141] <(SA1-2) Resin>

[0142] From the viewpoint of improving adhesion at extremely low temperatures of about -50°C and improving thermal cycle reliability, the (SA1) resin preferably contains (SA1-2) silicone resin and / or polysiloxane (hereinafter, "(SA1-2) resin").

[0143] As the (SA1-2) resin, for example, there can be mentioned a resin obtained by hydrolyzing one or more selected from difunctional organosilanes, trifunctional organosilanes, tetrafunctional organosilanes and monofunctional organosilanes and subjecting them to dehydration condensation. It should be noted that the (SA1-2) resin can also be hydrosilylated to introduce functional groups into the organic groups on the silicon atoms.

[0144] The organosilicon resin is a resin having a structural unit containing an organosilicon structure as the main skeleton. That is, a bifunctional organosilane unit having two organic groups on a silicon atom and bonded to two oxygen atoms is used as the main skeleton. In the organosilicon resin, the content ratio of the bifunctional organosilane unit in all organosilane units is 50 mol% or more, preferably 60 mol% or more, and more preferably 70 mol% or more. On the other hand, the content ratio of the above-mentioned bifunctional organosilane unit is preferably 100 mol% or less, more preferably 90 mol% or less, and more preferably 80 mol%.

[0145] Polysiloxane is a resin having a structural unit containing a siloxane structure as the main skeleton. That is, a trifunctional organosilane unit having one organic group on a silicon atom and bonded to three oxygen atoms is used as the main skeleton. In the organosilicon resin, the content ratio of the trifunctional organosilane unit in all organosilane units is 50 mol% or more, preferably 60 mol% or more, and more preferably 70 mol% or more. On the other hand, the content ratio of the above-mentioned trifunctional organosilane unit is preferably 100 mol% or less, more preferably 90 mol% or less, and more preferably 80 mol%.

[0146] The resin (SA1-2) preferably has one or more units selected from the following (3) and (4).

[0147] (3) a difunctional organosilane unit, a trifunctional organosilane unit, a tetrafunctional organosilane unit or a monofunctional organosilane unit having an aliphatic group

[0148] (4) A difunctional organosilane unit, a trifunctional organosilane unit, a tetrafunctional organosilane unit or a monofunctional organosilane unit having an aromatic group.

[0149] The silicone resin preferably comprises a difunctional organosilane unit having an aliphatic group and / or a difunctional organosilane unit having an aromatic group. In addition, the polysiloxane preferably comprises a trifunctional organosilane unit having an aliphatic group and / or a trifunctional organosilane unit having an aromatic group.

[0150] The aliphatic group possessed by the resin (SA1-2) is preferably an alkyl group. The number of carbon atoms in the alkyl group is preferably 1 or more, more preferably 2 or more, and further preferably 3 or more. On the other hand, the number of carbon atoms in the alkyl group is preferably 10 or less, more preferably 8 or less, and further preferably 6 or less. The alkyl group is preferably a methyl group, an ethyl group, a propyl group, a butyl group, or a hexyl group.

[0151] The number of carbon atoms of the aromatic group possessed by the resin (SA1-2) is preferably 6 or more, more preferably 7 or more, and further preferably 8 or more. On the other hand, the number of carbon atoms of the aromatic group is preferably 15 or less, more preferably 12 or less, and further preferably 10 or less. The aromatic group is preferably phenyl, tolyl, xylyl, phenoxy, tolyloxy, or xylyloxy.

[0152] From the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving the thermal cycle reliability, in the (SA1-2) resin, the total content ratio of the above-mentioned units (3) in all the organosilane units is preferably 70 mol% or more, more preferably 80 mol% or more, further preferably 85 mol% or more, and particularly preferably 90 mol% or more. On the other hand, from the viewpoint of improving the thermal cycle reliability, the total content ratio of the above-mentioned units (3) in all the organosilane units is preferably 100 mol% or less, more preferably 99 mol% or less, further preferably 97 mol% or less, and particularly preferably 95 mol% or less.

[0153] From the viewpoint of improving thermal cycle reliability, in the (SA1-2) resin, the total content ratio of the above-mentioned units (4) in all the organosilane units is preferably 1.0 mol% or more, more preferably 3.0 mol% or more, and further preferably 5.0 mol% or more. On the other hand, from the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving thermal cycle reliability, the total content ratio of the above-mentioned units (4) in all the organosilane units is preferably 20 mol% or less, more preferably 15 mol% or less, and further preferably 10 mol% or less.

[0154] The resin (SA1-2) preferably further has the following unit (5).

[0155] (5) A difunctional organosilane unit, a trifunctional organosilane unit, a tetrafunctional organosilane unit or a monofunctional organosilane unit having an epoxy group

[0156] The resin (SA1-2) preferably includes a bifunctional organosilane unit having an epoxy group and / or a trifunctional organosilane unit having an epoxy group.

[0157] From the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving the thermal cycle reliability, in the (SA1-2) resin, the total content ratio of the units of the above-mentioned (5) in all the organosilane units is preferably 1.0 mol% or more, more preferably 3.0 mol% or more, and further preferably 5.0 mol% or more. On the other hand, from the viewpoint of improving the thermal cycle reliability, the total content ratio of the units of the above-mentioned (5) in all the organosilane units is preferably 20 mol% or less, more preferably 15 mol% or less, and further preferably 10 mol% or less.

[0158] The above-mentioned (SA1-2) resin has excellent flexibility because it contains a structural unit of an organic silicon structure or a siloxane structure as the main skeleton, and is therefore suitable for adjusting the shear strain at -50°C to within the range of 0.70 to 20 and / or adjusting the elastic modulus at -50°C to within the range of 0.10 to 200 MPa.

[0159] <Other (SA) Binder Resins>

[0160] Film of the present invention may also contain other (SA) binder resins. Other (SA) binder resins are preferably maleimide resins, maleimide-styrene resins, maleimide-triazine resins, cardo resins, epoxy (methyl) acrylate resins, acrylic resins, phenolic resins, phenol aralkyl resins, polyhydroxystyrene, tetrafluoroethylene polymers, polyphenylene ether, liquid crystal polymers, cycloolefin polymers or benzocyclobutene resins. These resins may also use known resins. Other (SA) binder resins preferably have an acidic group or a structure derived from an acidic group, more preferably have an acidic group or a structure derived from an acidic group in the repeating unit of the resin. The exemplification and preferred description of the above-mentioned acidic group are also respectively the same as the acidic group possessed by the above-mentioned (SA) binder.

[0161] The maleimide resin is a resin having at least two maleimide groups in at least one of the main chain of the resin, the side chain of the resin, and the terminal of the resin. It should be noted that the maleimide resin is a resin different from a polyimide-based resin.

[0162] Examples of maleimide-styrene resins include resins obtained by free radical copolymerization of a styrene derivative and the above maleimide resins, and resins obtained by free radical copolymerization of a maleimide compound, a styrene derivative, and other copolymerization components such as a (meth)acrylic acid derivative.

[0163] As the maleimide-triazine resin, for example, a resin obtained by further reacting a compound having a triazine structure and / or an aromatic cyanate compound with the above maleimide resin can be mentioned. In addition, a resin obtained by reacting a maleimide compound with a compound having a triazine structure and / or an aromatic cyanate compound can also be mentioned.

[0164] As maleimide- The oxazine resin may include, for example, a benzoic acid-containing A resin obtained by reacting a compound having an oxazine structure with the above-mentioned maleimide resin. A resin obtained by reacting a compound with an oxazine structure.

[0165] From the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving the thermal cycle reliability, the total content ratio of the (SA1) resin in the total 100% by mass of the (SA) binder resin is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, and particularly preferably 80% by mass or more. On the other hand, from the viewpoint of improving the adhesion, the total content ratio of the (SA1) resin is preferably 100% by mass or less, more preferably 95% by mass or less, and further preferably 90% by mass or less.

[0166] The total content of the (SA) binder resin in the film is preferably 10% by volume or more, more preferably 15% by volume or more, and further preferably 20% by volume or more. On the other hand, the total content of the (SA) binder resin in the film is preferably 50% by volume or less, more preferably 40% by volume or less, and further preferably 30% by volume or less.

[0167] <(SB) Epoxy compound or compound having a structure derived from an epoxy compound>

[0168] The film of the present invention preferably contains (SB) an epoxy compound or a compound having a structure derived from an epoxy compound (hereinafter, "(SB) compound"). The (SB) compound may be an epoxy compound or a compound having a structure derived from an epoxy compound. The epoxy compound may be a compound in the composition used to form the film of the present invention. As described above, the (SB) compound is preferably a compound that can form a cross-linked structure with the (SA) binder resin or a compound that has formed a cross-linked structure.

[0169] The number of epoxy groups possessed by the (SB) compound is preferably 2 or more, and more preferably 3 or more. On the other hand, the number of the epoxy groups possessed by the compound is preferably 6 or less, and more preferably 4.

[0170] From the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving the thermal cycle reliability, the film of the present invention preferably contains the (SB) compound.

[0171] The (SB) compound contains one or more selected from (SB1) a compound having a structure containing an oxyalkylene group (hereinafter, "(SB1) compound"), (SB2) a compound having a structure containing at least two aromatic structures and having a structure containing an oxyalkylene group (hereinafter, "(SB2) compound"), and (SB3) a compound having a tertiary amine structure bonded to an arylene group and two divalent organic groups (hereinafter, "(SB3) compound"). The (SB1) compound, (SB2) compound, and (SB3) compound may be compounds having structures derived from each of the above compounds. It should be noted that the (SB1) compound is a compound different from the (SB2) compound and does not have a structure containing an aromatic structure.

[0172] The oxyalkylene group contained in the compound (SB1) is preferably divalent or more, and more preferably trivalent or more. On the other hand, the oxyalkylene group contained in the compound (SB1) is preferably hexavalent or less, and more preferably tetravalent or less.

[0173] The number of oxyalkylene groups possessed by the (SB1) compound is preferably 1 or more, more preferably 4 or more, further preferably 6 or more, and particularly preferably 10 or more. On the other hand, the number of the above-mentioned oxyalkylene groups is preferably 20 or less, more preferably 17 or less, and further preferably 15 or less. The number of carbon atoms of the oxyalkylene groups possessed by the (SB1) compound is preferably 1 or more, more preferably 2 or more. On the other hand, the number of carbon atoms of the above-mentioned oxyalkylene groups is preferably 6 or less, more preferably 4 or less, and further preferably 3 or less.

[0174] The compound (SB1) preferably includes one or more selected from the group consisting of a compound represented by the general formula (21) and a compound having a structure represented by the general formula (22).

[0175]

[0176] In the general formula (21) and the general formula (22), X 5 represents an alkylene group having 1 to 30 carbon atoms. m represents an integer of 1 to 20. * 1 ~* 4 Each independently represents a bonding point to other structures.

[0177] In the general formula (21) and the general formula (22), the alkylene group having 1 to 30 carbon atoms is preferably a methylene group, an ethylene group, a propylene group, a butylene group or a hexylene group. It should be noted that the alkylene group is a linear structure or a branched structure. The alkylene group may have a heteroatom and may be an unsubstituted body or a substituted body.

[0178] The structure of the (SB2) compound containing at least two aromatic structures is preferably bonded to at least two oxyalkylene groups, preferably a divalent or higher structure via these at least two oxyalkylene groups. The divalent or higher structure is more preferably trivalent or higher. On the other hand, the divalent or higher structure is preferably hexavalent or lower, more preferably tetravalent or lower.

[0179] The number of carbon atoms in the aromatic structure of the (SB2) compound is preferably 6 or more, more preferably 7 or more, and even more preferably 8 or more. On the other hand, the number of carbon atoms in the aromatic structure is preferably 15 or less, more preferably 12 or less, and even more preferably 10 or less. The number of aromatic structures in the (SB2) compound is preferably 2 or more, more preferably 3 or more. On the other hand, the number of aromatic structures is preferably 6 or less, and even more preferably 4 or less.

[0180] The structure containing at least two aromatic structures in the (SB2) compound preferably has a group connecting the at least two aromatic structures. The above-mentioned connecting group is preferably a direct bond, an alkylene group having 1 to 6 carbon atoms, a haloalkylene group having 1 to 6 carbon atoms, a cycloalkylene group having 4 to 10 carbon atoms, an arylene group having 6 to 15 carbon atoms, an oxyarylene group having 6 to 15 carbon atoms, an ether bond, a carbonyl group, a carboxylate bond, an amide bond, a urea bond, a carbamate bond, a sulfonyl group or a carbonate bond.

[0181] The number of oxyalkylene groups possessed by the (SB2) compound is preferably 2 or more, more preferably 4 or more, further preferably 6 or more, and particularly preferably 10 or more. On the other hand, the number of the above-mentioned oxyalkylene groups is preferably 20 or less, more preferably 17 or less, and further preferably 15 or less. The number of carbon atoms of the oxyalkylene groups possessed by the (SB2) compound is preferably 1 or more, more preferably 2 or more. On the other hand, the number of carbon atoms of the above-mentioned oxyalkylene groups is preferably 6 or less, more preferably 4 or less, and further preferably 3 or less.

[0182] The compound (SB2) preferably includes one or more selected from the group consisting of a compound represented by the general formula (23) and a compound having a structure represented by the general formula (24).

[0183]

[0184] In the general formula (23) and the general formula (24), X 6 and X 7 Each independently represents an alkylene group having 1 to 30 carbon atoms. 6Preferably, it is a direct bond, an alkylene group having 1 to 6 carbon atoms, a haloalkylene group having 1 to 6 carbon atoms, a cycloalkylene group having 4 to 10 carbon atoms, an arylene group having 6 to 15 carbon atoms, an oxyaryleneoxy group having 6 to 15 carbon atoms, an ether bond, a carbonyl group, a carboxylate bond, an amide bond, a urea bond, a carbamate bond, a sulfonyl group or a carbonate bond. 33 and R 34 Each independently represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 4 to 7 carbon atoms, an aryl group having 6 to 15 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a hydroxyl group, or a ring-forming group. The ring connected via the ring-forming group represents a monocyclic or condensed polycyclic hydrocarbon ring. a and b each independently represent an integer of 0 to 4. m and n each independently represent an integer of 1 to 20. * 1 ~* 4 Each independently represents a bonding point to other structures.

[0185] In the general formula (23) and the general formula (24), the alkyl group having 1 to 6 carbon atoms is preferably a methyl group, an ethyl group or a propyl group. The cycloalkyl group having 4 to 7 carbon atoms is preferably a cyclobutyl group, a cyclopentyl group or a cyclohexyl group. The aryl group having 6 to 15 carbon atoms is preferably a phenyl group, a tolyl group or a xylyl group. The alkoxy group having 1 to 6 carbon atoms is preferably a methoxy group, an ethoxy group or a propoxy group. The alkylene group having 1 to 30 carbon atoms is preferably a methylene group, an ethylene group, a propylene group, a butylene group or a hexyl group. The alkylene group having 1 to 6 carbon atoms is preferably a methylene group, an ethylene group or a propylene group. The cycloalkylene group having 4 to 7 carbon atoms is preferably a cyclobutylene group, a cyclopentylene group or a cyclohexylene group. It should be noted that the alkyl group and the alkylene group have a straight chain structure or a branched structure. The above-mentioned alkyl group, cycloalkyl group, aryl group, alkoxy group, alkylene group and cycloalkylene group may have a heteroatom and may be either an unsubstituted body or a substituted body.

[0186] The tertiary amine structure of the compound (SB3) is preferably a trivalent or higher structure bonded to an arylene group and two divalent organic groups via these arylene groups and two divalent organic groups. The trivalent or higher structure is preferably hexavalent or lower, more preferably tetravalent or lower.

[0187] The number of carbon atoms of the arylene group possessed by the (SB3) compound is preferably 6 or more, more preferably 7 or more, and further preferably 8 or more. On the other hand, the number of carbon atoms of the above arylene group is preferably 15 or less, more preferably 12 or less, and further preferably 10 or less. The number of aromatic rings in the arylene group possessed by the (SB3) compound is preferably 1 or more, more preferably 2 or more. On the other hand, the number of aromatic rings is preferably 6 or less, more preferably 4 or less, and further preferably 3 or less.

[0188] The (SB3) compound also preferably has an oxyalkylene group. As an embodiment in which the (SB3) compound has an oxyalkylene group, the arylene group in the (SB3) compound is preferably an arylene group bonded to an oxyalkylene group. In addition, the divalent organic group in the (SB3) compound is preferably a divalent aliphatic group, and more preferably an alkylene group. As an embodiment in which the (SB3) compound has an oxyalkylene group, the divalent aliphatic group in the (SB3) compound is preferably a divalent aliphatic group bonded to an oxyalkylene group.

[0189] The number of oxyalkylene groups possessed by the (SB3) compound is preferably 2 or more, more preferably 4 or more, further preferably 6 or more, and particularly preferably 10 or more. On the other hand, the number of the above-mentioned oxyalkylene groups is preferably 20 or less, more preferably 17 or less, and further preferably 15 or less. The number of carbon atoms of the oxyalkylene groups possessed by the (SB3) compound is preferably 1 or more, more preferably 2 or more. On the other hand, the number of carbon atoms of the above-mentioned oxyalkylene groups is preferably 6 or less, more preferably 4 or less, and further preferably 3 or less.

[0190] The compound (SB3) preferably includes one or more selected from the group consisting of a compound represented by the general formula (25) and a compound having a structure represented by the general formula (26).

[0191]

[0192] In general formula (25) and general formula (26), X 8 , X 9 and X 10 Each independently represents an alkylene group having 1 to 30 carbon atoms. 35 represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 4 to 7 carbon atoms, an aryl group having 6 to 15 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a hydroxyl group, or a ring-forming group. The ring connected via the ring-forming group represents a monocyclic or condensed polycyclic hydrocarbon ring. a represents an integer of 0 to 4. l, m, and n each independently represent an integer of 0 to 20. * 1 ~* 6 Each independently represents a bonding point to other structures.

[0193] In general formula (25) and general formula (26), the alkyl group having 1 to 6 carbon atoms is preferably a methyl group, an ethyl group or a propyl group. The cycloalkyl group having 4 to 7 carbon atoms is preferably a cyclobutyl group, a cyclopentyl group or a cyclohexyl group. The aryl group having 6 to 15 carbon atoms is preferably a phenyl group, a tolyl group or a xylyl group. The alkoxy group having 1 to 6 carbon atoms is preferably a methoxy group, an ethoxy group or a propoxy group. The alkylene group having 1 to 30 carbon atoms is preferably a methylene group, an ethylene group, a propylene group, a butylene group or a hexylene group. It should be noted that the alkyl group and the alkylene group have a straight chain structure or a branched structure. The above-mentioned alkyl group, cycloalkyl group, aryl group, alkoxy group and alkylene group may have heteroatoms and may be any of unsubstituted or substituted groups.

[0194] The above-mentioned (SB1) compounds, (SB2) and (SB3) compounds are suitable in that the shear strain at -50°C is adjusted to within the range of 0.70 to 20 by a soft skeleton derived from an oxyalkylene group, and / or the elastic modulus at -50°C is adjusted to within the range of 0.10 to 200 MPa. In addition, it can be considered that the (SB) compound acts as an anchor in the interface with the component at extremely low temperatures by the coordination ability to each component derived from the tertiary amine structure. Therefore, it is estimated that the followability to each component is improved, and the adhesion and cold and hot cycle reliability are improved.

[0195] When the (SA) binder resin is set to 100 parts by mass, the total content of the (SB1) compound, (SB2) and (SB3) compound in the film is preferably 0.10 parts by mass or more, more preferably 0.50 parts by mass or more, further preferably 1.0 parts by mass or more, further preferably 3.0 parts by mass or more, and particularly preferably 5.0 parts by mass or more. On the other hand, the total content of the (SB1) compound, (SB2) and (SB3) compound in the film is preferably 20 parts by mass or less, more preferably 15 parts by mass or less.

[0196] <(SC) Amine compound or compound having a structure derived from an amine compound>

[0197] The film of the present invention preferably contains (SC) an amine compound or a compound having a structure derived from an amine compound (hereinafter, "(SC) compound"). The (SC) compound may be an amine compound or a compound having a structure derived from an amine compound. The amine compound may be a compound in the composition used to form the film of the present invention. The (SC) compound is preferably a compound that can form a cross-linked structure with the above-mentioned (SB) compound or a compound that has formed a cross-linked structure. The cross-linked structure is preferably formed by reaction, and may be formed by heating, by irradiation with energy rays, etc., without particular limitation.

[0198] The number of amino groups possessed by the (SC) compound is preferably 2 or more, and more preferably 3 or more. On the other hand, the number of the amino groups is preferably 6 or less, and more preferably 4.

[0199] From the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving the thermal cycle reliability, the film of the present invention preferably contains a (SC) compound.

[0200] The (SC) compound contains (SC1) a compound having an organosilicon structure and / or a siloxane structure and having at least two alkylene groups bonded to silicon atoms in the organosilicon structure and / or the siloxane structure (hereinafter, "(SC1) compound"). The (SC1) compound may be a compound having a structure derived from the above-mentioned compound.

[0201] The organosilicon structure and siloxane structure possessed by the (SC1) compound are preferably bonded to at least two alkylene groups via divalent or higher structures of these alkylene groups. The divalent or higher structures are more preferably trivalent or higher. On the other hand, the divalent or higher structures are preferably hexavalent or lower, and more preferably tetravalent or lower.

[0202] The number of silicon atoms in the compound (SC1) is preferably 5 or more, more preferably 10 or more, further preferably 15 or more, and particularly preferably 20 or more. On the other hand, the number of silicon atoms in the compound (SC1) is preferably 30 or less, more preferably 27 or less, and further preferably 25 or less.

[0203] The organosilicon structure in the (SC1) compound is preferably a dialkyl organosilicon structure and / or a monoalkyl organosilicon structure. The number of carbon atoms in the alkyl group of the dialkyl organosilicon structure and the monoalkyl organosilicon structure is preferably 1 or more, more preferably 2 or more, and even more preferably 3 or more. On the other hand, the number of carbon atoms in the alkyl group is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less.

[0204] The siloxane structure in the compound (SC1) is preferably a monoalkylsiloxane structure. The number of carbon atoms in the alkyl group of the monoalkylsiloxane structure is preferably 1 or more, more preferably 2 or more, and further preferably 3 or more. On the other hand, the number of carbon atoms in the alkyl group is preferably 10 or less, more preferably 8 or less, and further preferably 6 or less.

[0205] The content ratio of the aliphatic group in the total of the aliphatic group and the aromatic group bonded to the silicon atom in the organosilicon structure and the siloxane structure in the (SC1) compound is preferably 80 mol% or more, more preferably 85 mol% or more, and further preferably 90 mol% or more. On the other hand, from the viewpoint of improving the thermal cycle reliability, the content ratio of the aliphatic group in the total of the aliphatic group and the aromatic group is preferably 100 mol% or less, more preferably 99 mol% or less, and further preferably 97 mol% or less.

[0206] The aliphatic group possessed by the (SC1) compound is preferably an alkyl group. The preferred number of carbon atoms of the alkyl group is also the same as above. The alkyl group is preferably a methyl group, an ethyl group, a propyl group, a butyl group or a hexyl group. The number of carbon atoms of the aromatic group possessed by the (SC1) compound is preferably 6 or more, more preferably 7 or more, and further preferably 8 or more. On the other hand, the number of carbon atoms of the aromatic group is preferably 15 or less, more preferably 12 or less, and further preferably 10 or less. The aromatic group is preferably a phenyl group, a tolyl group, a xylyl group, a phenoxy group, a tolyloxy group or a xylyloxy group.

[0207] The compound (SC1) preferably contains one or more selected from the group consisting of a compound represented by the general formula (31) and a compound having a structure represented by the general formula (32).

[0208]

[0209] In the general formula (31) and the general formula (32), X 11 and X 12 Each independently represents a direct bond, an oxygen atom, an alkylene group having 1 to 30 carbon atoms, an alkyleneoxy group having 1 to 30 carbon atoms, or an arylene group having 6 to 30 carbon atoms. 41 ~R 46 Each independently represents an alkyl group having 1 to 30 carbon atoms, an aryl group having 6 to 30 carbon atoms, or an aryloxy group having 6 to 30 carbon atoms. x represents an integer of 1 to 100. * 1 ~* 4 Each independently represents a bonding point to other structures.

[0210] In the general formula (31) and the general formula (32), the alkyl group having 1 to 30 carbon atoms is preferably a methyl group, an ethyl group, a propyl group, a butyl group or a hexyl group. The aryl group having 6 to 30 carbon atoms is preferably a phenyl group, a tolyl group or a xylyl group. The aryloxy group having 6 to 30 carbon atoms is preferably a phenoxy group, a tolyloxy group or a xylyloxy group. The alkylene group having 1 to 30 carbon atoms is preferably a methylene group, an ethylene group, a propylene group, a butylene group or a hexylene group. The arylene group having 6 to 30 carbon atoms is preferably a phenylene group, a tolylene group or a xylylene group. It should be noted that the alkyl group and the alkylene group have a straight chain structure or a branched structure. The above-mentioned alkyl group, aryl group, aryloxy group, alkylene group and arylene group may have heteroatoms and may be any of unsubstituted or substituted groups.

[0211] The above-mentioned compound (SC1) is suitable in that the shear strain at -50°C is adjusted to within the range of 0.70 to 20 and / or the elastic modulus at -50°C is adjusted to within the range of 0.10 to 200 MPa due to the flexible skeleton derived from the silicone structure and / or the siloxane structure.

[0212] When the total amount of the (SA) binder resin, the (SB) compound and the (SC) compound is 100 parts by mass, the content of the (SC1) compound in the film is preferably 1.0 parts by mass or more, more preferably 3.0 parts by mass or more, further preferably 5.0 parts by mass or more, and particularly preferably 6.0 parts by mass or more. On the other hand, the content of the (SC1) compound in the film is preferably 20 parts by mass or less, more preferably 15 parts by mass or less.

[0213] <(SD) Thermally conductive filler>

[0214] The film of the present invention contains (SD) thermally conductive filler. The so-called (SD) thermally conductive filler refers to inorganic particles having a thermal conductivity of 2.0 W / (m·K) or more at 25°C. The thermal conductivity can be obtained by measuring in accordance with "JIS R1611 (2010)" after obtaining a sintered body with a thickness of about 1.0 mm and a porosity of less than 10% by volume. It should be noted that in "7.2 Measurement Method" of "JIS R1611 (2010)", it is recorded that "c) the measurement of bulk density thermal diffusivity is based on "JIS R1634" (c) the measurement of bulk density thermal diffusivity is based on "JIS R1634" etc.), but for the measurement in the present invention, the measurement of "c) bulk density" refers to the value measured in accordance with "JIS R1634 (1998)".

[0215] It should be noted that the shape of the (SD) thermally conductive filler may be, for example, spherical, ball-like, flaky, flake-like, foil-like, fibrous or needle-like. From the viewpoint of improving the thermal conductivity of the film due to high-density filling of the filler, a spherical (SD) thermally conductive filler is preferred.

[0216] From the viewpoint of improving adhesion and improving thermal cycle reliability, the thermal conductivity of the (SD) thermally conductive filler at 25°C is preferably 2.0 W / (m·K) or more, more preferably 5.0 W / (m·K) or more, further preferably 10 W / (m·K) or more, further preferably 20 W / (m·K) or more, particularly preferably 30 W / (m·K) or more, and particularly preferably 40 W / (m·K) or more. On the other hand, from the viewpoint of improving thermal cycle reliability, the thermal conductivity of the (SD) thermally conductive filler at 25°C is preferably 300 W / (m·K) or less, more preferably 200 W / (m·K) or less, further preferably 150 W / (m·K) or less, and particularly preferably 100 W / (m·K) or less.

[0217] From the viewpoint of improving adhesion and improving thermal cycle reliability, the (SD) thermal conductive filler preferably contains aluminum, boron, silicon, magnesium, zinc, titanium, zirconium, yttrium or iron as the main component element, and more preferably contains aluminum, boron, silicon, magnesium or zinc as the main component element. It should be noted that the so-called main component element refers to the element that is contained most in the constituent components based on mass.

[0218] The (SD) thermally conductive filler preferably includes one or more selected from the group consisting of aluminum oxide particles, aluminum nitride particles, boron nitride particles, silicon dioxide particles, silicon carbide particles, silicon nitride particles, magnesium oxide particles, magnesium carbonate particles, magnesium hydroxide particles, zinc oxide particles, titanium carbide particles, titanium nitride particles, titanium oxide particles, zirconium oxide particles, yttrium oxide particles, and iron oxide particles.

[0219] The (SD) thermally conductive filler described above is suitable for adjusting the thermal conductivity of the film at 25° C. to within the range of 0.10 to 5.0 W / (m·K) while maintaining the mechanical properties of the film due to its strong structure and high thermal conductivity.

[0220] In a first aspect of the film of the present invention, the (SD) thermally conductive filler includes (SD1) a first thermally conductive filler and (SD2) a second thermally conductive filler.

[0221] (SD1) The average primary particle size of the first thermally conductive filler is 1.0 to 200 μm,

[0222] (SD2) The average primary particle size of the second thermally conductive filler is 0.010 μm or more and less than 1.0 μm.

[0223] In the second aspect of the film of the present invention, from the viewpoint of improving adhesion and improving thermal cycle reliability, the (SD) thermally conductive filler preferably includes (SD1) a first thermally conductive filler and (SD2) a second thermally conductive filler.

[0224] More preferably, (SD1) the average primary particle size of the first thermally conductive filler is 1.0 to 200 μm,

[0225] (SD2) The average primary particle size of the second thermally conductive filler is 0.010 μm or more and less than 1.0 μm.

[0226] From the viewpoint of high-density packing of the filler and clarification of the filler interface, the average primary particle size of the first thermally conductive filler (SD1) is preferably 2.0 μm or more, and more preferably 3.0 μm or more.

[0227] By adopting the above-mentioned structure, the filler with a small particle size fills the gaps between the fillers with a large particle size, so the effect of improving the thermal conductivity of the film due to the high-density filling of the filler becomes significant. In addition, it is estimated that the internal stress caused by the temperature rise of the component can be reduced by efficient heat dissipation, and the followability to each component is improved, so the adhesion and thermal cycle reliability are improved.

[0228] From the viewpoint of improving the reliability of thermal cycles, the average primary particle size of the first thermally conductive filler (SD1) is preferably 5.0 μm or more, more preferably 10 μm or more, further preferably 15 μm or more, further preferably 20 μm or more, particularly preferably 25 μm or more, and particularly preferably 30 μm or more. On the other hand, from the viewpoint of improving the adhesion, the above-mentioned average primary particle size is preferably 150 μm or less, more preferably 100 μm or less, and further preferably 80 μm or less. Furthermore, from the viewpoint of improving the adhesion at extremely low temperatures of around -50°C and improving the reliability of thermal cycles, it is preferably 60 μm or less, more preferably 50 μm or less, further preferably 45 μm or less, and particularly preferably 40 μm or less.

[0229] From the viewpoint of improving thermal cycle reliability, the average primary particle size of the second thermally conductive filler (SD2) is preferably 0.050 μm or more, more preferably 0.10 μm or more, further preferably 0.15 μm or more, and particularly preferably 0.20 μm or more. On the other hand, from the viewpoint of improving adhesion, the average primary particle size is preferably 0.80 μm or less, more preferably 0.60 μm or less, and further preferably 0.40 μm or less.

[0230] The so-called (SD) primary particle size of the thermally conductive filler refers to the major axis diameter of the primary particles of the filler. The average primary particle size of the (SD) thermally conductive filler in the film can be photographed and analyzed using a transmission electron microscope (hereinafter, "TEM") on the cross section of the film, and is calculated as the average value obtained by measuring 30 primary particles of the filler. It should be noted that the average primary particle size of the first thermally conductive filler (SD1) is the average value obtained by measuring 30 primary particles of the filler with a primary particle size of 1.0 μm or more in the measurement using TEM. In addition, the average primary particle size of the second thermally conductive filler (SD2) is the average value obtained by measuring 30 primary particles of the filler with a primary particle size of less than 1.0 μm in the measurement using TEM. The elements contained in the (SD) thermally conductive filler can be detected by photographing and analyzing the cross section of the film using a transmission electron microscope-energy dispersive X-ray spectroscopy (hereinafter, "TEM-EDX"). By using the measurement of TEM-EDX, it is also possible to distinguish two or more fillers and clarify the filler interface. The average primary particle size of the thermally conductive filler in the filler dispersion is determined by measuring the particle size distribution using a laser diffraction / scattering method. Examples of measuring instruments include SLD3100 manufactured by Shimadzu Corporation, LA-920 manufactured by Horiba, Ltd., or equivalents thereof.

[0231] From the viewpoint of improving adhesion, the specific surface area of ​​the first thermally conductive filler (SD1) is preferably 0.023 m 2 / g or more, more preferably 0.031m 2 / g or more, more preferably 0.047m 2 / g or more, particularly preferably 0.059m 2 Furthermore, from the viewpoint of improving the adhesion at an extremely low temperature of about -50°C and improving the thermal cycle reliability, 0.080 m 2 / g or more, more preferably 0.11m 2 / g or more, more preferably 0.15m 2 / g or more, more preferably 0.18m 2 / g or more, particularly preferably 0.20m 2 / g or more, particularly preferably 0.23m 2 In particular, from the viewpoint of improving the adhesion at an extremely low temperature of about -50°C, 0.18 m / g is preferred. 2 / g or more, more preferably 0.20m 2 / g or more, more preferably 0.23m 2 / g or above.

[0232] On the other hand, from the viewpoint of high-density packing of the filler and clear filler interface, the specific surface area of ​​the first thermally conductive filler (SD1) is preferably 5.90 m 2 / g or less, more preferably 3.00m 2 / g or less, more preferably 2.00m 2 / g or less. Furthermore, from the viewpoint of improving the reliability of thermal cycles, 1.20 m 2 / g or less, more preferably 1.00m 2 / g or less, more preferably 0.80m 2 / g or less, more preferably 0.60m 2 / g or less, particularly preferably 0.50m 2 / g or less, particularly preferably 0.40m 2 In particular, from the viewpoint of improving the adhesion at an extremely low temperature of about -50°C, 2.00 m / g or less is preferred. 2 / g or less, more preferably 1.20m 2 / g or less, more preferably 1.00m 2 / g or less, more preferably 0.80m 2 / g or less, more preferably 0.60m 2 / g or less, more preferably 0.50m 2 / g or less, particularly preferably 0.40m 2 / g or less.

[0233] By adopting the above-mentioned configuration, the anchoring effect brought about by the filler with a specific specific surface area reduces the inclination of the stress-strain curve in which the vertical axis is stress and the horizontal axis is strain (increase in strain per unit stress), and thus it is suitable to adjust the shear strain at -50°C to within the range of 0.70 to 20. Therefore, it is estimated that the flexibility that can alleviate the difference in thermal expansion coefficient between components even at extremely low temperatures improves the followability to each component, thereby improving the adhesion and thermal cycle reliability.

[0234] From the viewpoint of improving adhesion, the specific surface area of ​​the second thermally conductive filler (SD2) is preferably 5.91 m 2 / g or more, more preferably 8.00m 2 / g or more, more preferably 12.0m 2 / g or more, more preferably 14.6m 2 / g or more, particularly preferably 16.1 m 2 / g or more, particularly preferably 19.5m 2On the other hand, from the viewpoint of improving thermal cycle reliability, the specific surface area of ​​the second thermally conductive filler (SD2) is preferably 590 m 2 / g or less, more preferably 120m 2 / g or less, more preferably 60.0m 2 / g or less, more preferably 50.0m 2 / g or less, particularly preferably 40.0m 2 / g or less, particularly preferably 30.0m 2 / g or less.

[0235] It is believed that by adopting the above-mentioned structure, the filler with a small particle size fills the gaps between the fillers with a large particle size, so that the heat generated in the joined components can be dissipated efficiently, and the internal stress caused by the temperature rise of the components can be reduced. In addition, it is also estimated that the heat accumulated in the film can be reduced, and the change of mechanical properties caused by the temperature rise of the film can be suppressed.

[0236] The specific surface area of ​​the (SD) thermally conductive filler can be calculated by measuring the BET specific surface area by the gas adsorption method. First, the film is heated at 600-900°C to thermally decompose and / or volatilize the organic components such as the resin, and the mass of the remaining (SD) thermally conductive filler is measured. Next, the gas molecules are adsorbed and the BET specific surface area is calculated from the single molecule adsorption amount. It should be noted that the above-mentioned remaining (SD) thermally conductive filler is photographed and analyzed using a TEM, and the primary particle size of the filler is measured, so that it can be determined which one is equivalent to the (SD1) first thermally conductive filler and the (SD2) second thermally conductive filler. In addition, in the case where the above-mentioned remaining (SD) thermally conductive filler is a mixture of the (SD1) first thermally conductive filler and the (SD2) second thermally conductive filler, the two fillers can be separated by using a dry classifier or a wet classifier, so that the specific surface area of ​​each can be measured.

[0237] From the viewpoint of improving the adhesion and the reliability of the thermal cycle, when the total of the first thermally conductive filler (SD1) and the second thermally conductive filler (SD2) is 100% by volume, the content ratio of the first thermally conductive filler (SD1) is preferably 40% by volume or more, more preferably 50% by volume or more, and even more preferably 60% by volume or more. On the other hand, from the viewpoint of improving the adhesion and the reliability of the thermal cycle, the content ratio of the first thermally conductive filler (SD1) is preferably 80% by volume or less, more preferably 75% by volume or less, and even more preferably 70% by volume or less.

[0238] From the viewpoint of improving the adhesion and the reliability of the thermal cycle, when the total of the first thermally conductive filler (SD1) and the second thermally conductive filler (SD2) is 100 volume %, the content ratio of the second thermally conductive filler (SD2) is preferably 20 volume % or more, more preferably 25 volume % or more, and further preferably 30 volume % or more. On the other hand, from the viewpoint of improving the adhesion and the reliability of the thermal cycle, the content ratio of the first thermally conductive filler (SD1) is preferably 60 volume % or less, more preferably 50 volume % or less, and further preferably 40 volume % or less.

[0239] The film of the present invention may contain other (SD) thermally conductive fillers. Examples of other (SD) thermally conductive fillers include carbon black or metal fillers such as aluminum particles, magnesium particles, silver particles, zinc particles, iron particles, or lead particles.

[0240] The content ratio of the (SD) thermally conductive filler in the film is preferably 50% by volume or more, more preferably 60% by volume or more, and further preferably 70% by volume or more. On the other hand, the content ratio of the (SD) thermally conductive filler in the film is preferably 90% by volume or less, more preferably 85% by volume or less, and further preferably 80% by volume or less.

[0241] The content of the (SD) thermally conductive filler can be calculated using a method of measuring by thermogravimetric analysis or an equivalent method. The method includes first heating the film at 600 to 900°C to thermally decompose and / or volatilize the organic components such as the resin, measuring the mass of the remaining (SD) thermally conductive filler, and then calculating the mass of the organic components such as the resin from the difference. Then, the obtained mass is divided by the specific gravity of each to calculate the volume of the (SD) thermally conductive filler and the organic components such as the resin.

[0242] <Content of specific elements and specific ions in the film>

[0243] From the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving the reliability of cold and hot cycles, the film of the present invention preferably satisfies at least one of the following conditions (S1a), (S2a), (S3a), (S1b), (S2b) and (S3b). From the same viewpoint, the film of the present invention more preferably satisfies at least one of the following conditions (S1a), (S2a) and (S3a), and further preferably satisfies at least one of the following conditions (S1a), (S2a) and (S3a), and satisfies at least one of the following conditions (S1b), (S2b) and (S3b). When the following (S1a) is satisfied, the following (S1b) is preferably satisfied. When the following (S2a) is satisfied, the following (S2b) is preferably satisfied. When the following (S3a) is satisfied, the following (S3b) is preferably satisfied. It should be noted that, when the membrane of the present invention satisfies the following condition (S1b), it is preferred that the following condition (S1a) is satisfied by the ions containing the boron element in the membrane. In addition, when the membrane of the present invention satisfies the following condition (S2b), it is preferred that the following condition (S2a) is satisfied by the ions containing the phosphorus element in the membrane. In addition, when the membrane of the present invention satisfies the following condition (S3b), the following condition (S3a) is satisfied by the chloride ions and bromide ions in the membrane.

[0244] (S1a) The boron content in the film is 5.0 mass % or less

[0245] (S2a) The phosphorus content in the film is 1,000 mass ppm or less

[0246] (S3a) The total content of chlorine and bromine in the film is 1,000 mass ppm or less

[0247] (S1b) The total content of ions containing the boron element in the film is 5.0 mass % or less

[0248] (S2b) The total content of ions containing phosphorus in the film is 5,000 mass ppm or less

[0249] (S3b) The total content of chloride ions and bromide ions in the film is 1,000 mass ppm or less.

[0250] In the case of the above-mentioned configuration, the film of the present invention preferably contains the following (I) and / or (II).

[0251] (I) at least one selected from the group consisting of a component containing boron, a component containing phosphorus, a component containing chlorine, and a component containing bromine

[0252] (II) at least one selected from the group consisting of a component containing a boron-based cation, a component containing the following boron-based anions, a component containing a phosphorus-based cation, a component containing the following phosphorus-based anions, and a component containing the following halogen anions

[0253] Boron anion: one or more selected from borate ion, monohydrocarbyl borate ion, dihydrocarbyl borate ion, tetraphenyl borate ion, tetrafluoroborate ion and trifluoroborate ion

[0254] Phosphorus-based anions: one or more halogen anions selected from phosphate ion, phosphite ion, hypophosphite ion and hexafluorophosphate ion: chloride ion and / or bromide ion.

[0255] The content of boron in the film is preferably 0.010 mass % or more, more preferably 0.030 mass % or more, further preferably 0.050 mass % or more, further preferably 0.070 mass % or more, and particularly preferably 0.10 mass % or more. On the other hand, the content of boron in the film is preferably 4.0 mass % or less, more preferably 3.0 mass % or less, further preferably 2.0 mass % or less, and particularly preferably 1.0 mass % or less.

[0256] The content of phosphorus in the film is preferably 0.010 mass ppm or more, more preferably 0.030 mass ppm or more, further preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the content of phosphorus in the film is preferably 500 mass ppm or less, more preferably 300 mass ppm or less, further preferably 100 mass ppm or less, further preferably 50 mass ppm or less, further preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and particularly preferably 1.0 mass ppm or less.

[0257] The preferred range of the total content of the chlorine element and the bromine element in the film is also the same as the above-mentioned upper limit and lower limit of the content of the phosphorus element.

[0258] The total content of the ions containing the boron element in the film is preferably 0.010 mass % or more, more preferably 0.030 mass % or more, further preferably 0.050 mass % or more, further preferably 0.070 mass % or more, and particularly preferably 0.10 mass % or more. On the other hand, the total content of the ions containing the boron element in the film is preferably 4.0 mass % or less, more preferably 3.0 mass % or less, further preferably 2.0 mass % or less, and particularly preferably 1.0 mass % or less.

[0259] The total content of the ions containing phosphorus in the film is preferably 0.010 mass ppm or more, more preferably 0.030 mass ppm or more, further preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the total content of the ions containing phosphorus in the film is preferably 3,000 mass ppm or less, more preferably 1,000 mass ppm or less, further preferably 500 mass ppm or less, further preferably 300 mass ppm or less, further preferably 100 mass ppm or less, further preferably 50 mass ppm or less, further preferably 30 mass ppm or less, particularly preferably 10 mass ppm or less, and particularly preferably 5.0 mass ppm or less.

[0260] The total content of chloride ions and bromide ions in the film is preferably 0.010 mass ppm or more, more preferably 0.030 mass ppm or more, further preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.100 mass ppm or more. On the other hand, the total content of chloride ions and bromide ions in the film is preferably 500 mass ppm or less, more preferably 300 mass ppm or less, further preferably 100 mass ppm or less, further preferably 50 mass ppm or less, further preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and particularly preferably 1.0 mass ppm or less.

[0261] It can be considered that by being the above-mentioned structure, boron, phosphorus, chlorine or bromine interact with the surface of the member to be joined. It can be considered that boron has an empty 3p orbital, and by utilizing the electron acceptor of the empty orbital, it is easy to form a coordination bond from the surface of the member. In addition, it can be considered that phosphorus has a non-shared electron pair, and further by utilizing the efficient electron donation of the 3d orbital as an empty atomic orbital, it is easy to form a coordination bond on the surface of the relative member. In addition, it can be considered that chlorine and bromine have a large number of non-shared electron pairs, and by utilizing the electron donation of these electron pairs, it is easy to form a coordination bond on the surface of the member. It is presumed that by these effects, it acts as an anchor in the interface with the member at extremely low temperatures, so that the followability of each member is improved, and the adhesion and cold and hot cycle reliability are improved.

[0262] <Content of fluorine element and fluoride ion in the film>

[0263] From the viewpoint of improving the tightness at extremely low temperatures of about -50°C and improving the reliability of cold and hot cycles, the membrane of the present invention preferably satisfies at least one of the following conditions (S3α) and (S3β). From the same viewpoint, the membrane of the present invention more preferably satisfies the following condition (S3α), further preferably satisfies the following condition (S3α), and satisfies the following condition (S3β). It should be noted that when the membrane of the present invention satisfies the following condition (S3β), the following condition (S3α) is satisfied by the fluoride ions in the membrane.

[0264] (S3α) The content of fluorine in the film is 1,000 mass ppm or less

[0265] (S3β) The content of fluorine ions in the film is 1,000 mass ppm or less.

[0266] In the case of the above-mentioned configuration, the film of the present invention preferably contains the following (III) and / or (IV).

[0267] (III) Components containing fluorine

[0268] (IV) A component containing fluoride ions.

[0269] The content of fluorine in the film is preferably more than 0.000 mass ppm, more preferably more than 0.010 mass ppm, further preferably more than 0.030 mass ppm, further more preferably more than 0.050 mass ppm, particularly preferably more than 0.070 mass ppm, particularly preferably more than 0.10 mass ppm. On the other hand, the content of fluorine in the film is preferably less than 500 mass ppm, more preferably less than 300 mass ppm, further preferably less than 100 mass ppm, further preferably less than 50 mass ppm, further preferably less than 30 mass ppm, further preferably less than 10 mass ppm, further preferably less than 5.0 mass ppm, particularly preferably less than 3.0 mass ppm, particularly preferably less than 1.0 mass ppm.

[0270] The content of fluorine ions in the film is preferably more than 0.000 mass ppm, more preferably 0.010 mass ppm or more, further preferably 0.030 mass ppm or more, further preferably 0.050 mass ppm or more, particularly preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the content of fluorine ions in the film is preferably 500 mass ppm or less, more preferably 300 mass ppm or less, further preferably 100 mass ppm or less, further preferably 50 mass ppm or less, further preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and particularly preferably 1.0 mass ppm or less.

[0271] It is considered that the fluorine element has a large number of unshared electron pairs, and that by including the fluorine element in the film, electron donation by these electron pairs is utilized, thereby making it easier to form a coordinate bond with the surface of the member.

[0272] The content of fluorine in the film may be 0.000 mass ppm. The content of fluorine ions in the film may also be 0.000 mass ppm. When the content of fluorine and / or the content of fluorine ions in the film exceeds 0.000 mass ppm, the film of the present invention preferably has a fluorine atom or fluorine ion in the structure of the (SA) binder resin or the (SD) thermally conductive filler, or further contains a component containing fluorine and / or a component containing fluorine ions.

[0273] When the film of the present invention contains a (SB) compound or a (SC) compound, and the content of fluorine element and / or the content of fluorine ions in the film exceeds 0.000 mass ppm, the film of the present invention preferably has a (SA) binder resin, a (SD) thermally conductive filler, a (SB) compound or a (SC) compound having fluorine atoms or fluorine ions in its structure, or further contains a component containing a fluorine element and / or a component containing a fluorine ion.

[0274] It is speculated that by making the content of the compound containing fluorine atoms in the structure, the component containing fluorine element, etc. in the film below a specific value, the content of the fluorine element, fluorine ion or anion containing the fluorine element derived from these components in these components becomes below a specific value, so that the local interaction with the surface of the member to be joined is improved by the hydrogen bond of each component in the film, the electronegativity of the fluorine atom, etc. In addition, it can be considered that by intentionally making the content of the above-mentioned components below a specific value, the polarization structure and charge balance in the film are controlled, and the influence of ionic components, etc. that have an adverse effect on the mechanical properties of the film in the hot and cold cycle can be suppressed. It is speculated that through these effects, it acts as an anchor in the interface with the component at extremely low temperatures, so that the followability of each component is improved, and the adhesion and hot and cold cycle reliability are improved.

[0275] <Content of platinum element and content of ions containing platinum element in the film>

[0276] From the viewpoint of improving the tightness at extremely low temperatures of about -50°C and improving the reliability of cold and hot cycles, the membrane of the present invention preferably satisfies at least one of the following conditions (S4a) and (S4b). From the same viewpoint, the membrane of the present invention more preferably satisfies the following condition (S4a), further preferably satisfies the following condition (S4a), and satisfies the following condition (S4b). It should be noted that when the membrane of the present invention satisfies the following condition (S4b), the following condition (S4a) is satisfied by the ions containing the platinum element in the membrane.

[0277] (S4a) The content of platinum in the film is 1,000 mass ppm or less

[0278] (S4b) The total content of ions containing the platinum element in the film is 5,000 mass ppm or less.

[0279] In the case of the above-mentioned structure, the film of the present invention preferably contains a component containing a platinum element and / or a component containing a platinum cation. The component containing a platinum element is preferably a single substance of platinum or an organic platinum compound. The component containing a platinum cation is preferably a platinum halide, a platinum hydroxide, a platinum alkoxide compound, a platinum chelate or a platinum carboxylate.

[0280] The content of platinum in the film is preferably 0.010 mass ppm or more, more preferably 0.030 mass ppm or more, further preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the content of platinum in the film is preferably 500 mass ppm or less, more preferably 300 mass ppm or less, further preferably 100 mass ppm or less, further preferably 50 mass ppm or less, particularly preferably 30 mass ppm or less, and particularly preferably 10 mass ppm or less.

[0281] The total content of the ions containing the platinum element in the film is preferably 0.010 mass ppm or more, more preferably 0.030 mass ppm or more, further preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the total content of the ions containing the platinum element in the film is preferably 3,000 mass ppm or less, more preferably 1,000 mass ppm or less, further preferably 500 mass ppm or less, further preferably 300 mass ppm or less, particularly preferably 100 mass ppm or less, and particularly preferably 50 mass ppm or less.

[0282] It is believed that by adopting the above-mentioned structure, the platinum element is coordinated with the surface of the member to be joined, and acts as an anchor at the interface with the member at extremely low temperatures. Therefore, it is estimated that the followability to each member is improved, and the adhesion and thermal cycle reliability are improved.

[0283] <Content of specific silicon compound and content of cyclic organosilicon compound in film>

[0284] From the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving the reliability of cold and hot cycles, the film of the present invention preferably satisfies at least one of the following conditions (S5a) and (S5b). From the same viewpoint, the film of the present invention more preferably satisfies the following condition (S5a), further preferably satisfies the following condition (S5a), and satisfies the following condition (S5b).

[0285] (S5a) The total content of the organosilane compound having 1 to 2 silicon atoms (hereinafter, “specific silicon compound”) in the film is 1,000 mass ppm or less

[0286] (S5b) The total content of the cyclic organosilicon compounds in the film is 1,000 mass ppm or less.

[0287] The specific silicon compound preferably has a methyl group, a phenyl group, a hydroxyl group, an epoxy group, an amino group, a styryl group, a (meth)acryloyl group, a vinyl group, or an allyl group.

[0288] The number of silicon atoms in the cyclic organosilicon compound is preferably 4 or more, more preferably 6 or more, and further preferably 8 or more. It is particularly preferably 10 or more. On the other hand, the number of silicon atoms is preferably 20 or less, more preferably 16 or less, and further preferably 12 or less.

[0289] The above-mentioned specific silicon compound and cyclic organosilicon compound preferably have an alkoxy group and / or a silanol group. The total number of the above-mentioned alkoxy group and the silanol group is preferably 1 or more, more preferably 2 or more, and further preferably 3 or more. On the other hand, the total number of the above-mentioned alkoxy group and the silanol group is preferably 10 or less, more preferably 8 or less, and further preferably 6 or less.

[0290] The total content of the specific silicon compound in the film is preferably 0.010 mass ppm or more, more preferably 0.030 mass ppm or more, further preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the total content of the specific silicon compound in the film is preferably 500 mass ppm or less, more preferably 300 mass ppm or less, further preferably 100 mass ppm or less, further preferably 50 mass ppm or less, particularly preferably 30 mass ppm or less, and particularly preferably 10 mass ppm or less.

[0291] The total content of the cyclic organosilicon compounds in the film is preferably 0.010 mass ppm or more, more preferably 0.030 mass ppm or more, further preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the total content of the cyclic organosilicon compounds in the film is preferably 500 mass ppm or less, more preferably 300 mass ppm or less, further preferably 100 mass ppm or less, further preferably 50 mass ppm or less, particularly preferably 30 mass ppm or less, and particularly preferably 10 mass ppm or less.

[0292] It is believed that the above-mentioned specific silicon compound reacts with the hydroxyl group and / or silanol group on the surface of the component by adopting the above-mentioned structure. Therefore, it is estimated that the silicon compound acts as an anchor in the interface with the component at extremely low temperatures, so the followability to each component is improved, and the adhesion and thermal cycle reliability are improved.

[0293] <Crosslinking agent or compound having a structure derived from a crosslinking agent>

[0294] The film of the present invention preferably contains a crosslinking agent or a compound having a structure derived from a crosslinking agent (hereinafter, "crosslinking agent and other compounds"). The crosslinking agent and other compounds may be a crosslinking agent or a compound having a structure derived from a crosslinking agent. The crosslinking agent may be a compound in the composition used to form the film of the present invention. The so-called crosslinking agent refers to a compound having a crosslinking group, a free radical polymerizable group, a cationic polymerizable group or an anionic polymerizable group that can react with a resin or the like.

[0295] As mentioned above, the crosslinking agent and other compounds are preferably compounds that can form a crosslinked structure with the (SA) binder resin or compounds that have formed a crosslinked structure. The crosslinking agent preferably has at least two of the following groups: alkoxymethyl, hydroxymethyl, oxetane, blocked isocyanate, styryl, cinnamoyl, maleimide, nadicimide, (meth)acryloyl, vinyl or allyl. It should be noted that the crosslinking agent is a compound different from the above-mentioned (SB) compound, and can be a compound having an epoxy group different from the above-mentioned (SB) compound.

[0296] Compounds such as the above crosslinking agent are suitable for improving the mechanical properties of the film by forming a crosslinked structure with the (SA) binder resin. It is also estimated that the adhesion and the like are improved by the interaction with each member caused by the structure derived from the crosslinking agent.

[0297] <Curing accelerator or compound having a structure derived from a curing accelerator>

[0298] The film of the present invention preferably contains a curing accelerator or a compound having a structure derived from a curing accelerator (hereinafter, "a compound such as a curing accelerator"). The compound such as a curing accelerator may be a curing accelerator or a compound having a structure derived from a curing accelerator. The curing accelerator may be a compound in the composition used for forming the film of the present invention. The so-called curing accelerator refers to a compound having a structure that promotes the reaction of the above-mentioned (SB) compound or cross-linking agent.

[0299] Compounds such as curing accelerators are preferably compounds that can form a cross-linked structure with the above-mentioned (SB) compound or cross-linking agent or compounds that have formed a cross-linked structure. The cross-linked structure is preferably formed by reaction, by heating, by irradiation of energy rays, etc., without particular limitation. The curing accelerator preferably has an imidazole group, a polyphenol structure, anhydride group, a hydrazide group, a sulfhydryl group or a Lewis acid-amine coordination compound structure. It should be noted that the curing accelerator is a compound different from the above-mentioned (SC) compound, and can be a compound with an amino group different from the above-mentioned (SC) compound. The curing accelerator is also preferably a latent curing accelerator that frees the above-mentioned substituents and structures by reaction, heating or irradiation of energy rays.

[0300] Compounds such as the curing accelerator described above are suitable for improving the mechanical properties of the film by forming a crosslinked structure with the (SB) compound or the crosslinking agent. It is also estimated that the interaction with each member caused by the structure derived from the curing accelerator improves adhesion.

[0301] From the viewpoint of improving the adhesion at extremely low temperatures of around -50°C and improving thermal cycle reliability, the curing accelerator is preferably a compound having a silicone structure and / or a siloxane structure, having at least two alkylene groups bonded to the silicon atoms in the silicone structure or the siloxane structure, and further having an acid anhydride group (hereinafter, "specific acid anhydride compound").

[0302] The organosilicon structure and siloxane structure possessed by the specific acid anhydride compound are preferably combined with at least two alkylene groups, through a structure of divalence or more of these alkylene groups. The number of silicon atoms possessed by the specific acid anhydride compound is preferably 5 or more, more preferably 10 or more, further preferably 15 or more, and particularly preferably 20 or more. On the other hand, the number of silicon atoms possessed by the specific acid anhydride compound is preferably 30 or less. The organosilicon structure in the specific acid anhydride compound is preferably a dialkyl organosilicon structure and / or a monoalkyl organosilicon structure. The siloxane structure in the specific acid anhydride compound is preferably a monoalkyl siloxane structure.

[0303] The above-mentioned specific acid anhydride compound is suitable for adjusting the shear strain at -50°C to within the range of 0.70 to 20 and / or adjusting the elastic modulus at -50°C to within the range of 0.10 to 200 MPa by means of a flexible skeleton derived from an organic silicon structure or a siloxane structure.

[0304] <Other compounds or compounds having structures derived from other compounds>

[0305] The film of the present invention may contain other compounds or compounds having structures derived from other compounds. These compounds may be other compounds or compounds having structures derived from other compounds. Other compounds may be compounds in the composition for forming the film of the present invention. Other compounds are preferably metal alkoxide compounds, metal chelates or surfactants.

[0306] Metal alkoxide compounds and metal chelates preferably contain titanium, zirconium, aluminum, magnesium, zinc, indium, tin or copper as the element of main component. The above-mentioned metal alkoxide compounds and metal chelates are suitable in the cross-linked structure formed by (SA) binder resin, (SB) compound or cross-linking agent, so that the mechanical properties of film are improved. In addition, it is estimated that these compounds work as anchors in the interface with components, so that adhesion etc. are improved.

[0307] The surfactant is preferably a fluororesin surfactant, a silicone surfactant or an acrylic resin surfactant. The surfactant described above is suitable for joining other components on the surface of the film by suppressing the protrusions on the surface of the film. It is estimated that by suppressing the protrusions on such a surface, the adhesion is improved by increasing the contact area with other components, interacting with each other, etc.

[0308] <Solvent>

[0309] When the film of the present invention is in a semi-cured state (B stage) described later, a part of the solvent may remain. Regarding the solvent, a part of the solvent in the composition used for forming the film of the present invention may remain. The solvent is preferably a compound having an alcoholic hydroxyl group, a carbonyl group, an ester bond, an amide bond or at least three ether bonds.

[0310] <Method for producing film of the present invention>

[0311] The method for producing the composition for forming the film of the present invention is exemplified by adding a resin, various additives, a filler component, and a solvent, mixing them using a stirrer, a kneader, etc., and then mixing them using a bead mill, a three-roll mill, etc.

[0312] The method for producing the film of the present invention is exemplified. The method includes forming a coating film of the composition on a support described later by coating, printing, etc., and then, if necessary, drying the coating film under reduced pressure to distill off the solvent, and then heating the coating film at 40 to 150° C. Then, if necessary, a protective film described later may be laminated on the formed film.

[0313] <Film physical properties>

[0314] In the first embodiment of the film of the present invention, the elastic modulus at -50°C is preferably 0.10 to 200 MPa. In the second embodiment of the film of the present invention, the elastic modulus at -50°C is 0.10 to 200 MPa. From the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving the reliability of cold and hot cycles, the elastic modulus at -50°C in the film of the present invention is preferably 0.10 MPa or more, more preferably 0.30 MPa or more, further preferably 0.50 MPa or more, further preferably 0.70 MPa or more, and particularly preferably 1.0 MPa or more. On the other hand, from the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving the reliability of cold and hot cycles, the elastic modulus at -50°C is preferably 200 MPa or less, more preferably 130 MPa or less, and further preferably 100 MPa or less. Further, the elastic modulus at -50°C is preferably 50 MPa or less, more preferably 30 MPa or less, further preferably 10 MPa or less, and particularly preferably 5.0 MPa or less.

[0315] It is estimated that by adopting the above-mentioned structure, the internal stress caused by the difference in thermal expansion coefficient between the components joined by the film can be reduced by low elastic modulus at an extremely low temperature of about -50°C, and the followability of each component can be improved, thereby improving the tightness and thermal cycle reliability.

[0316] The thermal conductivity of the film of the present invention at 25°C is 0.10 to 5.0 W / (m·K). From the viewpoint of improving adhesion and improving thermal cycle reliability, the thermal conductivity at 25°C in the film of the present invention is preferably 0.30 W / (m·K) or more, more preferably 0.50 W / (m·K) or more, further preferably 0.70 W / (m·K) or more, and particularly preferably 1.0 W / (m·K) or more. On the other hand, from the viewpoint of improving thermal cycle reliability, the thermal conductivity at 25°C is preferably 4.0 W / (m·K) or less, more preferably 3.0 W / (m·K) or less, further preferably 2.5 W / (m·K) or less, and particularly preferably 2.0 W / (m·K) or less.

[0317] In the first embodiment of the film of the present invention, the shear strain at -50°C is 0.70 to 20. In the second embodiment of the film of the present invention, the shear strain at -50°C is preferably 0.70 to 20. From the viewpoint of improving the adhesion at extremely low temperatures of around -50°C and improving the reliability of thermal cycles, the shear strain at -50°C in the film of the present invention is preferably 1.0 or more, more preferably 1.5 or more, further preferably 2.0 or more, and particularly preferably 2.5 or more. On the other hand, from the viewpoint of improving the adhesion at extremely low temperatures of around -50°C and improving the reliability of thermal cycles, the shear strain at -50°C is preferably 17 or less, more preferably 15 or less, further preferably 12 or less, and particularly preferably 10 or less.

[0318] It is presumed that the above-described configuration provides flexibility capable of relaxing the difference in thermal expansion coefficient between components even at extremely low temperatures, thereby improving the followability to each component and thus improving the adhesion and thermal cycle reliability.

[0319] From the viewpoint of improving adhesion, the thickness of the film of the present invention is preferably 5.0 μm or more, more preferably 20 μm or more, further preferably 50 μm or more, further preferably 100 μm or more, and particularly preferably 150 μm or more. On the other hand, from the viewpoint of improving thermal cycle reliability, the thickness of the film of the present invention is preferably 500 μm or less, more preferably 400 μm or less, further preferably 350 μm or less, and particularly preferably 300 μm or less.

[0320] <Laminate>

[0321] Hereinafter, the laminate of the present invention will be described. It should be noted that, when described as the laminate of the present invention, it is a common description of the first and third schemes of the laminate of the present invention having the film of the present invention. On the other hand, when describing a laminate of a specific scheme, it is recorded as the first scheme of the laminate of the present invention, etc. However, the present invention is not limited to the following embodiments, and various changes can be made within the scope of being able to achieve the purpose of the invention and not exceeding the main purpose of the invention.

[0322] <Film and laminate in semi-cured state>

[0323] From the viewpoint of improving adhesion, the elastic modulus at 25°C in the film of the present invention is preferably 0.010 MPa or more, more preferably 0.050 MPa or more, further preferably 0.10 MPa or more, and particularly preferably 0.30 MPa or more. On the other hand, from the viewpoint of improving adhesion, the elastic modulus at 25°C is preferably 1.0 MPa or less, more preferably 0.70 MPa or less, and further preferably 0.50 MPa or less.

[0324] From the viewpoint of improving adhesion, the film of the present invention is preferably in a semi-cured state (B stage). The so-called semi-cured state refers to a situation or state in which a cross-linked structure is not formed, or a cross-linked structure is formed by a partial reaction, but the film has fluidity. For example, after being applied to a substrate, the coating film is dried under reduced pressure to remove the solvent by distillation, or the coating film is heated at 40 to 150° C. to dry it, which means a state soluble in an organic solvent or an alkaline solution.

[0325] The first embodiment of the laminate of the present invention is a laminate having a support and the film of the present invention, wherein the film of the present invention is disposed on the support. In the first embodiment of the laminate of the present invention, the elastic modulus of the film at 25° C. is preferably 0.010 to 1.0 MPa, and the film is preferably in a semi-cured state.

[0326] The above-described configuration is suitable from the viewpoint of improving adhesion and handling properties, and is suitable for disposing the film on a base member or a ceramic dielectric member described later.

[0327] <Support body>

[0328] In the first embodiment of the laminate of the present invention, there is a support. From the viewpoint of improving the adhesion to the film, flexibility and operability, the support is preferably a flexible substrate. The flexible substrate is preferably a polyimide substrate, a polyphenylene sulfide substrate, a silicone substrate, an acrylic resin substrate, an epoxy resin substrate, a polyethylene terephthalate substrate, a polybutylene terephthalate substrate, a polyethylene naphthalate substrate or a polycarbonate substrate. The support may also be a rigid substrate. As a rigid substrate, for example, a glass substrate, a quartz substrate, a crystal substrate or a sapphire substrate may be cited. From the viewpoint of improving the adhesion to the film and improving the peelability, the surface of the film side of the support may be surface treated with a silane coupling agent or the like. From the viewpoint of operability, the thickness of the support is preferably 10 to 200 μm.

[0329] In the first aspect of the laminate of the present invention, from the viewpoint of improving handling properties and protecting the surface of the film, a laminate having a first support, the film of the present invention and a second support in this order is preferred. In addition, the first support and the second support preferably have different thicknesses.

[0330] The exemplification and preferred description of the first support and the second support are also respectively the same as those of the above-mentioned support. The second support is preferably a protective film, preferably a polyethylene film, a polypropylene film, a polyester film, a polyethylene terephthalate film, a polybutylene terephthalate film or a polyethylene naphthalate film. From the viewpoint of operability, the second support preferably has little adhesion to the film.

[0331] <Embodiment 1 of Laminated Body>

[0332] A schematic cross-sectional view of a configuration example of the first embodiment of the laminate is shown in Figure 1 middle. Figure 1 The laminate 100A shown is a laminate having a first support 10, a film 30 of the present invention, and a second support 20 in this order. The first support 10 and the second support 20 are as described above. The film 30 is a film of the present invention, and is preferably in a semi-cured state (B stage). The film 30 is preferably a layer formed by a composition for forming a film of the present invention.

[0333] <Film and laminate as cured product of composition>

[0334] The film of the present invention is preferably a cured product of the composition. The composition is preferably a composition for forming the film of the present invention. Curing refers to a situation or state where a cross-linked structure is formed by reaction and the fluidity of the film disappears. The reaction is carried out by heating, by irradiation with energy rays, etc., without particular limitation, but preferably carried out by heating. The state where a cross-linked structure is formed by heating and the fluidity of the film disappears is called thermal curing.

[0335] As heating conditions, for example, conditions such as heating at 150 to 500° C. for 5 to 300 minutes are mentioned. As heating methods, for example, methods of heating using an oven, a hot plate, infrared rays, a rapid annealing device, or a laser annealing device can be cited. As processing atmospheres, for example, air, oxygen, nitrogen, helium, neon, argon, krypton, or xenon atmospheres, gas atmospheres containing 1.0 mass ppm or more and less than 10,000 mass ppm of oxygen (0.00010 mass % or more and less than 1.0 mass %), gas atmospheres containing 10,000 mass ppm (1.0 mass %) or more of oxygen, or vacuum can be cited.

[0336] The film of the present invention can have both high adhesion and high thermal cycle reliability for joining components to each other even at an extremely low temperature of about -50°C. Therefore, the film of the present invention is preferably used in a substrate processing step at a temperature below 0°C, and is more preferably used in the formation of a laminate in which a substrate processing step is performed at a temperature below 0°C. The temperature of the substrate processing step using the laminate is more preferably -20°C, more preferably below -40°C, more preferably below -50°C, and particularly preferably below -60°C. On the other hand, the temperature of the above-mentioned substrate processing step is preferably above -150°C, more preferably above -100°C, and more preferably above -80°C. The substrate processing step is preferably one or more selected from sputtering, evaporation, chemical vapor deposition, ion implantation, etching, polishing, exposure and inspection.

[0337] It should be noted that the film of the present invention can also be used in a substrate treatment process at a temperature exceeding 0° C., and can also be used to form a laminated body in which a substrate treatment process is performed at a temperature exceeding 0° C. In this case, the temperature of the substrate treatment process using the laminated body is preferably 20° C. or higher, more preferably 40° C. or higher, and further preferably 60° C. or higher. On the other hand, the temperature of the above-mentioned substrate treatment process is preferably 150° C. or lower, more preferably 100° C. or lower, and further preferably 80° C. or lower.

[0338] The film preferably has a plurality of through holes. The through holes are preferably formed by perforation, press processing, laser processing, laser direct imaging, laser direct structuring, printing, inkjet, etching or photolithography.

[0339] The second embodiment of the laminate of the present invention is a laminate having a base member, the film of the present invention and a ceramic dielectric member in this order, wherein the base member and the ceramic dielectric member have different thermal expansion coefficients. In the second embodiment of the laminate of the present invention, the film is preferably a cured product of the composition. In the second embodiment of the laminate of the present invention, the elastic modulus of the film at 25° C. is preferably 0.010 to 1.0 MPa, and the film is also preferably in a semi-cured state.

[0340] The above-described configuration is suitable from the viewpoint of improving adhesion when the base member and the ceramic member are bonded together, and the effect of suppressing separation of the members becomes significant even when the base member and the ceramic dielectric member have different thermal expansion coefficients.

[0341] From the viewpoint of improving adhesion and heat dissipation efficiency in the substrate processing step, the difference in thermal expansion coefficient between the base member and the ceramic dielectric member is preferably 1.0 ppm / K or more, more preferably 5.0 ppm / K or more, and even more preferably 10 ppm / K or more. On the other hand, the difference in thermal expansion coefficient is preferably 30 ppm / K or less, more preferably 25 ppm / K or less, and even more preferably 20 ppm / K or less.

[0342] <Content of specific elements and specific ions in the film of the laminate>

[0343] From the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving the thermal cycle reliability, the film possessed by the laminate of the present invention preferably satisfies at least one of the conditions (S1a), (S2a), (S3a), (S1b), (S2b) and (S3b) as the film of the present invention. In the case of the above-mentioned structure, the film possessed by the laminate of the present invention preferably contains the above-mentioned (I) and / or (II) as the film of the present invention.

[0344] The preferred range of the content of the boron element in the film of the laminate, the preferred range of the content of the phosphorus element, and the preferred range of the total content of the chlorine element and the bromine element in the film of the laminate are also the same as those of the film of the present invention. The preferred range of the total content of the ions containing the boron element, the preferred range of the total content of the ions containing the phosphorus element, and the preferred range of the total content of the chlorine ion and the bromine ion in the film of the laminate are also the same as those described above.

[0345] From the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving the thermal cycle reliability, the film of the laminate of the present invention preferably satisfies at least one of the conditions (S4a) and (S4b) above, similarly to the film of the present invention. In the case of the above-mentioned structure, the film of the laminate of the present invention preferably contains a component containing a platinum element and / or a component containing a platinum cation, similarly to the film of the present invention.

[0346] The preferred range of the content of the platinum element in the film of the laminate is also the same as that of the film of the present invention. The preferred range of the total content of ions containing the platinum element in the film of the laminate is also the same as that of the film of the present invention.

[0347] <Content of the specific silicon compound and content of the cyclic organosilicon compound in the film of the laminate>

[0348] From the viewpoint of improving the adhesion at extremely low temperatures of about -50°C and improving the thermal cycle reliability, the film of the laminate of the present invention preferably satisfies at least one of the conditions (S5a) and (S5b) described above, as does the film of the present invention. In the case of the above-mentioned structure, the examples and preferred descriptions related to the specific silicon compound and the cyclic organosilicon compound are also as described above.

[0349] The preferred range of the total content of the specific silicon compound in the film of the laminate and the preferred range of the total content of the cyclic organic silicon compound are also the same as described above.

[0350] <Base member>

[0351] In the second embodiment of the laminate of the present invention, there is a base member. The base member is preferably formed of metal and various composite materials. The metal is preferably aluminum, titanium or their alloys. The composite material is preferably a material in which an aluminum alloy containing aluminum as a main component is melted and pressurized to infiltrate a porous ceramic containing silicon carbide as a main component. The aluminum alloy in the composite material may contain silicon or magnesium, and may also contain other elements.

[0352] <Ceramic dielectric components>

[0353] In the second embodiment of the laminate of the present invention, there is a ceramic dielectric component. The ceramic dielectric component is preferably a flat substrate made of sintered ceramic. From the viewpoint of mechanical strength, wear resistance, plasma resistance, thermal conductivity and insulation, the ceramic dielectric component preferably contains one or more selected from aluminum oxide (aluminum oxide: Al2O3), aluminum nitride, silicon carbide, silicon nitride and yttrium oxide (yttrium oxide: Y2O3), and more preferably contains aluminum oxide or aluminum nitride as the main component. It should be noted that the so-called main component refers to the component that is contained the most in terms of mass among the constituent components.

[0354] <Embodiment 2 of Laminated Body>

[0355] A schematic cross-sectional view of a configuration example of the second embodiment of the laminate is shown in Figure 2 middle. Figure 2 The laminated body 200A shown is a laminated body having a base member 40, a film 60 of the present invention, and a ceramic dielectric member 50 in this order. The base member 40 and the ceramic dielectric member 50 are as described above. The film 60 is a film of the present invention, and is preferably a cured product of a composition. The film 60 is preferably a layer formed of a composition for forming a film of the present invention.

[0356] <Electrostatic chuck with laminated body>

[0357] The electrostatic chuck of the present invention comprises a laminate having the film of the present invention. In addition, the film of the present invention can have both high adhesion for bonding components to each other even at an extremely low temperature of about -50°C, and high thermal cycle reliability. Therefore, the film of the present invention is preferably used in a substrate processing step at a temperature below 0°C, and more preferably used in the formation of an electrostatic chuck in a substrate processing step at a temperature below 0°C. That is, the film of the present invention is suitable for use in electrostatic chucks. In addition, the film of the present invention is particularly suitable for use in electrostatic chucks used below 0°C, and further, is particularly suitable for use in electrostatic chucks used below -50°C. The preferred range of temperature for the substrate processing step using the electrostatic chuck is also the same as the temperature for the substrate processing step using the above-mentioned laminate. The substrate processing step is preferably selected from one or more of sputtering, evaporation, chemical vapor deposition, ion implantation, etching, polishing, exposure and inspection.

[0358] It should be noted that the film of the present invention can also be used in a substrate processing step at a temperature exceeding 0° C., and can also be used to form an electrostatic chuck in a substrate processing step at a temperature exceeding 0° C. In this case, the preferred range of the temperature of the substrate processing step using the electrostatic chuck is also the same as the temperature of the substrate processing step using the above-mentioned laminate.

[0359] <Articles with laminated bodies>

[0360] The laminate of the present invention can be applied to various articles. As such an article, it is preferred to have an electrostatic chuck having the laminate of the present invention. As an article having a laminate as described above or an article having an electrostatic chuck, for example, an electronic device, a mobile body, a building or a window can be mentioned. As an electronic device, for example, a display device, a semiconductor device, a metal-clad laminate, an industrial device, a medical device or a building device can be mentioned. As a mobile body, for example, a vehicle, a railway, an airplane or a heavy machinery can be mentioned. As a building, for example, a residence, a store, an office, a building or a factory can be mentioned. As a window, for example, an electronic device window, a mobile body window or a building window can be mentioned.

[0361] <Plasma processing apparatus including a laminate>

[0362] The plasma processing device of the present invention comprises a plasma generating source and a laminate of the present invention. The plasma processing device of the present invention preferably comprises a plasma generating source and an electrostatic chuck comprising the laminate of the present invention. Such a configuration is suitable from the viewpoint of improving the aspect ratio in the etching process and reducing the process time, and is preferably used for high density / high integration of 3D-NAND memory and the like.

[0363] The plasma processing apparatus of the present invention is an apparatus that places a substrate to be processed, such as a semiconductor wafer, on a laminated body (preferably an electrostatic chuck) disposed in a vacuum chamber, applies a high-frequency voltage in a vacuum environment to generate plasma, and performs etching, etc. The electrostatic chuck in the plasma processing apparatus is a laminated body in which a ceramic dielectric member having a built-in heating electrode and an electrostatic electrode and a base member as a cooling plate having a cooling medium flow path formed therein are bonded by a film.

[0364] In a plasma processing device, a stage for placing a semiconductor wafer is provided inside a vacuum chamber, and the stage is mainly composed of an electrostatic chuck and a cooler for controlling the temperature of the electrostatic chuck. In recent years, high processing accuracy is required in the manufacture of semiconductor devices, and etching processing at an extremely low temperature below -30°C is required to form through holes with a high aspect ratio. Therefore, it is necessary to cool the base member serving as a cooling plate to below -30°C to cool the ceramic dielectric member. The film of the present invention that joins them can reduce the thermal resistance at the interface of the two members, thereby improving the cooling efficiency.

[0365] <Articles having films and articles having laminates>

[0366] The article having the film of the present invention and the laminate having the film of the present invention are also suitable when used for applications other than electrostatic chucks. Other applications include, for example, vacuum chucks in addition to the articles exemplified above.

[0367] <Method for producing laminate>

[0368] The method for producing a laminated body of the present invention comprises a step of disposing a base member, a step of disposing the film of the present invention, and a step of disposing a ceramic dielectric member.

[0369] The step of disposing the film of the present invention is preferably after the step of disposing the base member, and is preferably disposed on the base member. That is, the method for manufacturing the laminate of the present invention preferably includes the step of disposing the film of the present invention after the step of disposing the base member, and the step of disposing the ceramic dielectric member after the step of disposing the film of the present invention.

[0370] The step of arranging the film of the present invention is also preferably performed after the step of arranging the ceramic dielectric member, and is also preferably arranged on the ceramic dielectric member. That is, the method for manufacturing the laminated body of the present invention also preferably includes the step of arranging the film of the present invention after the step of arranging the ceramic dielectric member, and the step of arranging the base member after the step of arranging the film of the present invention.

[0371] <Step of arranging base member>

[0372] The process of configuring the base member is preferably a process of configuring the base member on the article, and is also preferably a process of configuring the base member fixed to the article. In the case where the process of configuring the base member is after the process of configuring the film of the present invention, it is preferably configured on the film of the present invention. In addition, the process of configuring the base member is also preferably a process of forming the base member on a support, and after configuring the base member with the support, peeling the support from the base member. The base member with the support is preferably configured by bonding with an adhesive or the like.

[0373] Examples of articles include electronic devices, mobile bodies, buildings, and windows. Examples of electronic devices include display devices, semiconductor devices, metal-clad laminates, industrial devices, medical devices, and building devices. Examples of mobile bodies include vehicles, railways, airplanes, and heavy machinery. Examples of buildings include residences, shops, offices, buildings, and factories. Examples of windows include electronic device windows, mobile body windows, and building windows.

[0374] The base member may be a commercially available metal member. The step of arranging the base member may be a step of arranging a commercially available metal member as the base member on the article.

[0375] <Step of placing ceramic dielectric members>

[0376] The process of configuring the ceramic dielectric component is preferably a process of configuring the ceramic dielectric component on an article. In the case where the process of configuring the ceramic dielectric component is after the process of configuring the film of the present invention, it is preferably configured on the film of the present invention. In addition, the process of configuring the ceramic dielectric component is also preferably a process of forming the ceramic dielectric component on a support, and after configuring the ceramic dielectric component with a support, peeling the support from the ceramic dielectric component. The ceramic dielectric component with a support is preferably configured by bonding with an adhesive or the like. As articles, for example, the articles exemplified in the above-mentioned base member can be cited.

[0377] The ceramic dielectric member may be a commercially available ceramic member. The step of arranging the ceramic dielectric member may be a step of arranging a commercially available ceramic member as the ceramic dielectric member on an article.

[0378] <Membranes placement process>

[0379] The process of configuring the film of the present invention is preferably a process of thermocompression bonding the film of the present invention, preferably thermocompression bonding on a base member. Similarly, thermocompression bonding on a ceramic dielectric member is also preferred. In addition, the process of configuring the above-mentioned base member is also preferably thermocompression bonding on the film of the present invention. Similarly, the process of configuring the above-mentioned ceramic dielectric member is also preferably thermocompression bonding on the film of the present invention. The method of thermocompression bonding is preferably hot pressing treatment, hot lamination treatment or hot vacuum lamination treatment.

[0380] When using the film of the present invention having the first support and the second support, it is preferred to dispose the film of the present invention after peeling off the second support. The first support can be peeled off after disposing the film of the present invention, and the film of the present invention can also be peeled off in the middle of being joined by a method such as thermocompression bonding or after being joined.

[0381] Example

[0382] The present invention is further specifically described below by giving examples, reference examples and comparative examples, but the present invention is not limited to these scopes. It should be noted that, for compounds using abbreviations among the compounds used in the following description or table, the names corresponding to the abbreviations are shown below. It should be noted that the structures of KF-8010, X-22-161A, X-22-161B, X-22-168A and X-22-168AS are shown below. It should be noted that the so-called main component refers to the component that is most contained based on mass in the constituent components.

[0383] ABPS: Bis(3-amino-4-hydroxyphenyl)sulfone

[0384] BAHF: 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane

[0385] BAP: 2,2-bis(3-amino-4-hydroxyphenyl)propane

[0386] BAPF: 9,9-bis(3-amino-4-hydroxyphenyl)fluorene

[0387] cyEpoTMS: 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane

[0388] DMeDMS: dimethyldimethoxysilane

[0389] DPhDMS: diphenyldimethoxysilane

[0390] KF-8010: dimethyl silicone modified with amino groups at both ends represented by general formula (11a) (x=7 to 11 as main component), number average molecular weight: 860, amino equivalent: 430 g / mol

[0391] MePhDMS: methyldimethoxysilane

[0392] MeTMS: Methyltrimethoxysilane

[0393] ODPA: 4,4'-oxydiphthalic anhydride

[0394] PET: Polyethylene terephthalate

[0395] PhTMS: Phenyltrimethoxysilane

[0396] TEGDM: triethylene glycol dimethyl ether

[0397] X-22-161A: dimethyl silicone modified with amino groups at both ends represented by general formula (11a) (x=15 to 23 as main component), number average molecular weight: 1,600, amino group equivalent: 800 g / mol

[0398] X-22-161B: dimethyl silicone modified with amino groups at both ends represented by general formula (11a) (x=32 to 44 as main component), number average molecular weight: 3,000, amino group equivalent: 1,500 g / mol

[0399] X-22-168A: dimethyl silicone modified with carboxylic anhydride groups at both ends represented by general formula (12a) (y=18 to 26 as main component), number average molecular weight: 2,000, acid anhydride equivalent: 1,000 g / mol

[0400] X-22-168AS: dimethyl silicone modified with carboxylic anhydride groups at both ends represented by the general formula (12a) (y=6 to 10 as the main component), number average molecular weight: 1,000, anhydride group equivalent: 500 g / mol.

[0401]

[0402] <Synthesis Examples of Each Resin>

[0403] As the (SA) binder resin, the compositions of the resins obtained in Synthesis Examples 1 to 19 are summarized in Tables 1 and 2.

[0404] Synthesis Example 1 Synthesis of polyimide (PI-1)

[0405] A 300 mL four-necked flask was equipped with a stirrer, a thermometer, a nitrogen inlet tube, and a dropping funnel, and 40.00 g (0.040 mol; 100 mol% relative to all carboxylic acid residues; mol ratio based on anhydride groups = 100) of X-22-168AS and 79.33 g of TEGDM were weighed and dissolved under a stream of dry nitrogen, and stirred at 60° C. Subsequently, 7.33 g (0.020 mol; 50 mol% relative to all amine residues; mol ratio based on amino groups = 50) of BAHF and 32.00 g (0.020 mol; 50 mol% relative to all amine residues; mol ratio based on amino groups = 50) of X-22-161A were added while stirring at 60° C., and stirred for 1 hour. Then, the temperature was raised to 180°C and stirred for 3 hours, and then cooled to room temperature to obtain a polyimide (PI-1) solution having a solid content concentration of 50% by mass. The obtained polyimide had a weight average molecular weight of 29,000 and an imidization ratio of 99%.

[0406] In Synthesis Examples 2 to 11, each resin was synthesized into polyimides (PI-2) to (PI-11) by appropriately changing the monomer compounds and copolymerization ratios of the monomers by the method described in Synthesis Example 1. The copolymerization ratios of the monomers are shown in Table 1.

[0407] Synthesis Example 12 Synthesis of Silicone Resin (SR-1)

[0408] In a three-necked flask, DMeDMS 52.30 g (87 mol%), DPhDMS 2.73 g (3 mol%), MeTMS 3.41 g (5 mol%), cyEpoTMS 6.16 g (5 mol%), and PGMEA 61.63 g were added. Air was flowed in the flask at 0.05 L / min, and the mixed solution was heated to 40°C in an oil bath while stirring. While the mixed solution was further stirred, an aqueous phosphoric acid solution obtained by dissolving 0.194 g of phosphoric acid in 19.37 g of water was added over 10 minutes. After the addition was completed, the silane compound was hydrolyzed by stirring at 40°C for 30 minutes. After the hydrolysis was completed, the bath temperature was set to 70°C and stirred for 1 hour, and then the bath temperature was raised to 115°C. After the start of the temperature rise, the internal temperature of the solution reached 100°C after about 1 hour, and then heated and stirred for 2 hours (internal temperature was 100-110°C). The resin solution obtained by heating and stirring for 2 hours was cooled in an ice bath to obtain a silicone resin (SR-1) solution having a solid content concentration of 40% by mass. The weight average molecular weight of the obtained silicone resin was 4,000.

[0409] In Synthesis Examples 13 to 15, silicone resins (SR-2) to (SR-4) were synthesized by appropriately changing the monomer compounds and copolymerization ratios of the respective resins by the method described in Synthesis Example 12. The copolymerization ratios of the monomers are shown in Table 2.

[0410] Synthesis Example 16 Synthesis of polysiloxane (PS-1)

[0411] In a three-necked flask, 38.82 g (57 mol%) of MeTMS, 2.97 g (3 mol%) of PhTMS, 21.04 g (35 mol%) of DMeDMS, 6.16 g (5 mol%) of cyEpoTMS, and 57.15 g of PGMEA were added. Air was flowed in the flask at 0.05 L / min, and the mixed solution was stirred while being heated to 40°C in an oil bath. While the mixed solution was further stirred, an aqueous phosphoric acid solution obtained by dissolving 0.207 g of phosphoric acid in 24.33 g of water was added over 10 minutes. After the addition was completed, the silane compound was hydrolyzed by stirring at 40°C for 30 minutes. After the hydrolysis was completed, the bath temperature was set to 70°C and stirred for 1 hour, and then the bath temperature was raised to 115°C. After the start of the temperature rise, the internal temperature of the solution reached 100°C after about 1 hour, and then heated and stirred for 2 hours (internal temperature was 100-110°C). The resin solution obtained by heating and stirring for 2 hours was cooled in an ice bath to obtain a polysiloxane (PS-1) solution having a solid content concentration of 40% by mass. The weight average molecular weight of the obtained polysiloxane was 5,500.

[0412] In Synthesis Examples 17 to 19, each resin was synthesized into polysiloxanes (PS-2) to (PS-4) by appropriately changing the monomer compounds and copolymerization ratios of the monomers by the method described in Synthesis Example 16. The copolymerization ratios of the monomers are shown in Table 2.

[0413] [Table 1]

[0414]

[0415] [Table 2]

[0416]

[0417] Regarding the resins obtained in the respective synthesis examples and the resins used in the respective examples, reference examples, and comparative examples, the structural units and structures of the respective resins are shown below.

[0418] Polyimide (PI-1)~(PI-7)

[0419] These polyimides have a main chain including a polyimide structure, a diamine residue having a structure represented by the general formula (11), and a tetracarboxylic anhydride residue having a structure represented by the general formula (12). The contents of fluorine element in the resin structures of these polyimides are 29,300 mass ppm for (PI-1), 15,600 mass ppm for (PI-2), 4,700 mass ppm for (PI-3), 3,100 mass ppm for (PI-4), 3,300 mass ppm for (PI-5), 5,400 mass ppm for (PI-6), and 6,200 mass ppm for (PI-7).

[0420] Polyimide (PI-8)~(PI-10)

[0421] These polyimides have a main chain including a polyimide structure, a diamine residue having a structure represented by the general formula (11), and a tetracarboxylic anhydride residue having a structure represented by the general formula (12).

[0422] The content of fluorine element in the structure of these polyimides and resins was 0.000 mass ppm.

[0423] Polyimide (PI-11)

[0424] The polyimide has a main chain including a polyimide structure. The content of fluorine element in the resin structure of the polyimide is 168,500 mass ppm.

[0425] Silicone resin (SR-1)~(SR-4)

[0426] These silicone resins have a main chain including a silicone resin structure, a difunctional organosilane unit and a trifunctional organosilane unit having an aliphatic group, a trifunctional organosilane unit having an aromatic group, and a trifunctional organosilane unit having an epoxy group.

[0427] Polysiloxane (PS-1)~(PS-4)

[0428] These polysiloxanes have a main chain including a polysiloxane structure, a difunctional organosilane unit and a trifunctional organosilane unit having an aliphatic group, a trifunctional organosilane unit having an aromatic group, and a trifunctional organosilane unit having an epoxy group.

[0429] <Evaluation Methods in Examples, Reference Examples, and Comparative Examples>

[0430] The evaluation methods in each of Examples, Reference Examples and Comparative Examples are shown below.

[0431] (1) Weight average molecular weight of resin

[0432] The polyimides (PI-1) to (PI-11) were prepared by dissolving each resin in N-methyl-2-pyrrolidone to prepare a 0.10 mass % N-methyl-2-pyrrolidone solution. The weight average molecular weight in terms of polystyrene was measured under the following measurement conditions using a GPC analyzer (Waters 2690; manufactured by Waters).

[0433] <GPC measurement conditions>

[0434] Detector: Waters 996

[0435] System controller: Waters 2690

[0436] Column oven: Waters HTR-B

[0437] Thermal Controller: Waters TCM

[0438] Column: TOSOH Guard Column

[0439] Column: TOSOH TSK-GELα-4000

[0440] Column: TOSOH TSK-GELα-2500

[0441] Mobile phase: N-methyl-2-pyrrolidone dissolved with 0.050 mol / L lithium chloride and phosphoric acid, respectively

[0442] Development speed: 0.40 mL / min.

[0443] The above silicone resins (SR-1) to (SR-4) and the above polysiloxanes (PS-1) to (PS-4) were determined by measuring the weight average molecular weight in terms of polystyrene by a method near room temperature based on "JIS K7252-3 (2008)" using a GPC analyzer (HLC-8220; manufactured by Tosoh Corporation) and tetrahydrofuran or N-methyl-2-pyrrolidone as a mobile phase.

[0444] (2) Imidization rate of polyimide

[0445] The infrared absorption spectrum of each polyimide was measured using a Fourier transform infrared spectrophotometer (FT-720; manufactured by Horiba, Ltd.) to confirm the presence or absence of an absorption peak (1,780 cm-1) of the imide structure of the polyimide. -1 Nearby peaks and 1,377cm -1The polyimide precursor structures (polyamic acid structure and polyamic acid ester structure, etc.) in each polyimide were imide-closed. The infrared absorption spectrum of each polyimide after heating was measured, and the peaks at 1,377 cm before and after heating were compared. -1 The peak intensity of the polyimide after heating was set as the imidization rate 100%, and the imidization rate of the polyimide before heating was calculated.

[0446] (3) Average primary particle size of filler in filler dispersion

[0447] Each filler was dispersed in methanol to prepare a methanol dispersion. The particle size distribution of each filler was measured by laser diffraction / scattering method using a laser diffraction / scattering particle size distribution measuring device (LA-920; manufactured by Horiba, Ltd.). From the particle size distribution, D50, at which the cumulative particle size distribution from the small particle size side of the volume basis becomes 50%, was calculated. The number of measurements was set to 2, and the average value was set to the average primary particle size of the filler in the filler dispersion.

[0448] (4) Average primary particle size of filler in the film

[0449] A film with a thickness of 250 μm as a cured film of the composition was prepared on a PET film with a thickness of 38 μm by the method described in Example 1 below. The PET film was peeled off, and the cross section of the film was photographed and analyzed using a transmission electron microscope to measure the primary particle size of the filler. The average value obtained by measuring 30 primary particles of the filler was calculated as the average primary particle size of the filler in the film.

[0450] (5) Volume content ratio of filler in film

[0451] The film was heated at 800°C to thermally decompose and / or volatilize the organic components such as resin. The mass of the remaining filler was measured, and the mass of the organic components such as resin was calculated from the difference. The obtained mass was divided by the specific gravity of each component to obtain the volume of each component. The total volume of each component was set to 100% by volume, and the volume content ratio of the filler was calculated.

[0452] (6) Contents of boron, phosphorus, chlorine, bromine and fluorine in the film

[0453] The contents of boron, phosphorus, chlorine, bromine and fluorine were measured by combustion ion chromatography under the following measurement conditions. The membrane was burned / decomposed in the combustion tube of the analysis device, and the generated gas was absorbed in the absorption liquid. Then, a part of the absorption liquid was analyzed by ion chromatography. The absence of an element content means that the element was not detected.

[0454] <Combustion / Absorption Conditions>

[0455] System: AQF-2100H, GA-210 (Mitsubishi Chemical Corporation)

[0456] Electric furnace temperature: inlet 900℃, outlet 1000℃

[0457] Gas: Ar / O2 200mL / min, O2 400mL / min

[0458] Absorption liquid: H2O2 0.1 mass%

[0459] Absorption volume: 5mL

[0460] <Ion Chromatography / Anion Analysis Conditions>

[0461] System: ICS1600 (manufactured by DIONEX)

[0462] Mobile phase: 2.7mmol / L Na2CO3, 0.3mmol / L NaHCO3

[0463] Flow rate: 1.50mL / min

[0464] Detector: Conductivity detector

[0465] Injection volume: 100 μL.

[0466] (7) Platinum content in the film

[0467] The content of platinum element was measured by inductively coupled plasma mass spectrometry and inductively coupled plasma emission spectrometry using a calibration curve obtained from a standard substance.

[0468] (8) Specific ion content in the membrane

[0469] The contents of ions containing boron, ions containing phosphorus, chloride ions, bromide ions, ions containing platinum, and fluoride ions were measured by ion chromatography under the following measurement conditions. The membrane was added to a 10 mmol / L potassium hydroxide aqueous solution and shaken for 2 hours to extract the ion components. After filtering the extract under the following conditions, the cation components and anion components were analyzed by ion chromatography. The absence of a record of the ion content means that the ion was not detected.

[0470] <Filtration treatment conditions>

[0471] Membrane filter: PVDF (Merck Millipore Co., Ltd.)

[0472] Column for solid-phase extraction: InertSep Slim-J PLS-3 (manufactured by GL Sciences Inc.)

[0473] Cation exchange column: OnGuard II H (manufactured by Thermo Fisher Scientific)

[0474] <Ion chromatography analysis conditions>

[0475] Device: ICS-5000 + (manufactured by Thermo Fisher Scientific)

[0476] Separation column: IonPac AS11-HC-4μm

[0477] Eluent: Potassium hydroxide / gradient

[0478] Detector: Conductivity detector

[0479] Sample injection volume: 100 μL.

[0480] (9) Thermal conductivity of the film

[0481] Using the method described in Example 1 below, a film with a thickness of 250 μm of a cured film as a composition was formed on a PET film with a thickness of 38 μm. The PET film was peeled off, and the thermal diffusivity of the film was measured using a laser flash method thermal diffusivity measurement device (LFA447; manufactured by Netzsch). In addition, the specific gravity of the film was measured by the Archimedes method, and the specific heat of the film was measured by differential scanning calorimetry. The thermal conductivity at 25°C was calculated from the obtained measurement values and the following formula.

[0482] Thermal conductivity [W / (m·K)] = Thermal diffusivity [m 2 / s] × Specific gravity [kg / m 3 × Specific heat [J / (kg·K)].

[0483] (10) Elastic modulus of the film

[0484] Using the method described in Example 1 below, a film with a thickness of 250 μm of a cured film as a composition was formed on a PET film with a thickness of 38 μm. The PET film was peeled off, the film was cut into a shape with a width of 5.0 mm × a length of 30 mm, and the elastic modulus of the film was measured using a dynamic viscoelasticity measurement device (DVA-200; manufactured by IT Measurement & Control). The measurement conditions were set such that the heating rate was 5.0°C / minute, the measurement frequency was 1 Hz, the storage elastic modulus at each temperature from -100 to 300°C was measured, and the elastic modulus at -50°C was obtained.

[0485] (11) Shear strain and shear adhesion strength of the film (joint adhesion)

[0486] By the method described in Example 1 below, a semi-cured film of the composition was prepared on a PET film of thickness 38 μm in such a way that the thickness of the cured film became 250 μm. The laminated body formed with the semi-cured film was cut into a shape of width 12.5 mm × length 25 mm, and heat-laminated at 60°C and 0.10 MPa on an aluminum plate of width 25 mm × length 100 mm × thickness 1.6 mm. Next, the PET film was peeled off, and an aluminum plate of width 25 mm × length 100 mm × thickness 1.6 mm was laminated, and heat-pressed at 180°C and 0.50 MPa for 1 hour to prepare a laminated body. A shear test was performed on the obtained laminated body based on "JIS K6850" using a universal testing machine (AGX-V; manufactured by Shimadzu Corporation). The test conditions were set to -50°C, the tensile speed to 2.0 mm / min, and the stress and shear deformation at break were measured. The shear strain at -50°C was calculated from the shear deformation, and the stress at break was defined as the shear adhesive strength at -50°C as an index of joint adhesion. The evaluation was made as follows: A+, A, B+, B, C+, and C, which had a shear adhesive strength of 0.5 MPa or more, were considered acceptable; A+, A, B+, and B, which had a shear adhesive strength of 1.5 MPa or more, were considered good; and A+ and A, which had a shear adhesive strength of 1,000 or more, were considered excellent.

[0487] A+: Shear bond strength is 3.0 or above

[0488] A: Shear bond strength is 2.5 or more and less than 3.0

[0489] B+: Shear bond strength is 2.0 or more and less than 2.5

[0490] B: Shear bond strength is 1.5 or more and less than 2.0

[0491] C+: Shear bond strength is 1.0 or more and less than 1.5

[0492] C: Shear bond strength is 0.5 or more and less than 1.0

[0493] D: Shear bond strength is 0.1 or more and less than 0.5

[0494] E: The shear bond strength is less than 0.1 or cannot be measured.

[0495] (12) Reliability of membrane thermal cycling

[0496] By the method described in Example 1 below, a semi-cured film of the composition was prepared on a 38 μm thick PET film so that the thickness of the cured film was 250 μm. The laminated body having the cured film was cut into shape, in The aluminum plate with a thickness of 3.0 mm was subjected to heat lamination at 60°C and 0.10 MPa. The alumina substrate with a thickness of 3.0 mm was laminated and hot-pressed at 120°C and 0.50 MPa for 24 hours to produce a laminate. An ultrasonic flaw detector (FS300; manufactured by Hitachi Power Solutions) was used to observe whether there were peeling locations in the obtained laminate. In addition, by visual inspection of the appearance, the presence of cracks in the alumina substrate was observed. Next, a thermal cycle test was carried out using a thermal shock tester (TSE-11; manufactured by Espec). The test conditions were to set 30 minutes of treatment at -65°C and 30 minutes of treatment at 100°C as one cycle, and the presence of peeling locations in the laminate after 250 cycles, 500 cycles, and 1,000 cycles was observed. In addition, by visual inspection of the appearance, the presence of cracks in the alumina substrate was observed. As an indicator of thermal cycle reliability, the number of cycles in which peeling, cracking, etc. occurred in the laminate and the alumina substrate was measured. It should be noted that if peeling, cracking, etc. occurred after the manufacture of the laminate, the above-mentioned thermal cycle test was not performed, and the number of cycles was set to 0. In addition, if peeling, cracking, etc. did not occur after 1,000 cycles, the number of cycles was set to >1,000. The judgment was made as follows: A+, A, B, and C with more than 250 cycles were qualified, A+, A, and B with more than 500 cycles were good, and A+ and A with more than 1,000 cycles were excellent.

[0497] A+: No peeling, cracking, etc. after 1,000 cycles

[0498] A: The number of cycles before peeling, cracking, etc. occurred is 1,000

[0499] B: The number of cycles at which peeling, cracking, etc. occurred is 500

[0500] C: The number of cycles at which peeling, cracking, etc. occurred is 250

[0501] D: Peeling, cracking, etc. occurred after the laminate was produced, and the number of cycles was 0.

[0502] <Compounds used in Examples, Reference Examples, and Comparative Examples>

[0503] As the (SD) thermally conductive fillers used in each of the Examples, Reference Examples, and Comparative Examples, a list and description of (sd-1) to (sd-10) are collectively shown below.

[0504] [(SD) Thermally conductive filler]

[0505] (sd-1): alumina particles (average primary particle size in filler dispersion: 3.0 μm, thermal conductivity: 20 W / (m·K), specific surface area: 1.62 m 2 / g)

[0506] (sd-2): alumina particles (average primary particle size in filler dispersion: 45 μm, thermal conductivity: 26 W / (m·K), specific surface area: 0.108 m 2 / g)

[0507] (sd-3): Aluminum nitride particles (average primary particle size in filler dispersion: 30 μm, thermal conductivity: 170 W / (m·K), specific surface area: 0.196 m 2 / g)

[0508] (sd-4): alumina particles (average primary particle size in filler dispersion: 0.40 μm, thermal conductivity: 20 W / (m·K), specific surface area: 12.2 m 2 / g)

[0509] (sd-5): alumina particles (average primary particle size in filler dispersion: 10 μm, thermal conductivity: 26 W / (m·K), specific surface area: 0.486 m 2 / g)

[0510] (sd-6): alumina particles (average primary particle size in filler dispersion: 60 μm, thermal conductivity: 26 W / (m·K), specific surface area: 0.081 m 2 / g)

[0511] (sd-7): aluminum nitride particles (average primary particle size in filler dispersion: 10 μm, thermal conductivity: 170 W / (m·K), specific surface area: 0.589 m 2 / g)

[0512] (sd-8): aluminum nitride particles (average primary particle size in filler dispersion: 50 μm, thermal conductivity: 170 W / (m·K), specific surface area: 0.118 m 2 / g)

[0513] (SD-9): Alumina particles (average primary particle size in filler dispersion: 0.20 μm, thermal conductivity: 20 W / (m·K), specific surface area: 24.3 m 2 / g)

[0514] (SD-10): Alumina particles (average primary particle size in filler dispersion: 0.80 μm, thermal conductivity: 20 W / (m·K), specific surface area: 6.08 m 2 / g).

[0515] In addition, the compounds corresponding to (sb-1) as the (SB) compound used in each example, reference example and comparative example; (sc-1), (sc-2), (sc-3) and (sc-4) as the (SC) compounds; (ad-1) as the curing accelerator; and (r-1) as the amine compound used in the comparative example are also summarized and shown below.

[0516] [(SB) compound]

[0517] (sb-1) is a bifunctional epoxy compound having a structure containing an oxyalkylene group represented by the general formula (21a), and its main component is m = 10.3. The weight average molecular weight of (sb-1) is 870, and the epoxy equivalent is 435 g / mol.

[0518]

[0519] [(SC) Compound]

[0520] (sc-1): KF-8010

[0521] (sc-2):X-22-161A

[0522] (sc-3):X-22-161B

[0523] (sc-4): 1,3-bis(3-aminopropyl)tetramethyldisiloxane

[0524] [Curing accelerator]

[0525] (ad-1): 2-phenyl-4-methylimidazole

[0526] [Amine compounds]

[0527] (r-1): 3,3'-Diaminodiphenyl sulfone.

[0528] In addition, compounds containing boron, phosphorus, chlorine, bromine, platinum or fluorine, and compounds containing ions containing boron, ions containing phosphorus, chlorine ions, bromide ions, ions containing platinum or fluorine ions (hereinafter referred to as "specific element compounds") used in each of the embodiments, reference examples and comparative examples; the above-mentioned specific silicon compounds; and the compounds corresponding to the above-mentioned cyclic organosilicon compounds are also shown below.

[0529] (B-1): Triphenyl borate

[0530] (B-2): Tetraethylammonium tetrafluoroborate

[0531] (P-1): Triphenylphosphine

[0532] (P-2): Tetraethylammonium phosphate

[0533] (Cl-1): Benzyl chloride

[0534] (Cl-2):Tetraethylammonium chloride

[0535] (Br-1): Benzyl bromide

[0536] (Br-2):Tetraethylammonium bromide

[0537] (Pt-1): Platinum

[0538] (Pt-2): Platinum(II) acetylacetonate

[0539] (Si-1): Dimethyldimethoxysilane

[0540] (Si-2): diphenyldimethoxysilane

[0541] (Si-3): Octamethylcyclotetrasiloxane

[0542] (Si-4): Octaphenylcyclotetrasiloxane

[0543] (F-1): Dodecyl fluoride

[0544] (F-2): (Butyltriethyl)ammonium fluoride.

[0545] <Preparation of film-forming composition>

[0546] Compositions 1 to 67 used for film formation were prepared using the compositions described in Tables 3 to 10. The values ​​in parentheses in Tables 3 to 10 represent the mass fraction of the solid content of each component. After mixing the components, the kneading was repeated 5 times using a triple roll mill to obtain a composition as a viscous liquid. Compositions 1 to 67 contain TEGDM contained in the above-mentioned polyimide solutions as a solvent, and compositions 22 to 29 contain PGMEA contained in the above-mentioned silicone resin solutions or the above-mentioned polysiloxane solutions as a solvent.

[0547] In addition, the solid content concentration of Composition 1 was 87 mass %.

[0548] The addition amount of the specific element compound was adjusted so that the contents of the boron element, phosphorus element, chlorine element, bromine element, platinum element and fluorine element in the composition, and the contents of the ions containing the boron element, the ions containing the phosphorus element, the chlorine ions, the bromine ions, the ions containing the platinum element and the fluorine ions became the compositions described in Tables 3 to 10. The addition amount of the specific silicon compound and the cyclic organosilicon compound was adjusted so that the compositions described in Tables 3 to 10 became.

[0549] [Table 3]

[0550] Table 3

[0551]

[0552] Average primary particle size in the filler dispersion of sd-1: 3.0 μm

[0553] Average primary particle size in sd-4 filler dispersion: 0.40 μm

[0554] [Table 4]

[0555]

[0556] [Table 5]

[0557]

[0558] [Table 6]

[0559]

[0560] [Table 7]

[0561]

[0562] [Table 8]

[0563]

[0564] [Table 9]

[0565]

[0566] [Table 10]

[0567]

[0568] <Example 1>

[0569] <Preparation of samples for film evaluation>

[0570] Composition 1 was applied to a 38 μm thick PET film using a comma roll coater so that the thickness of the cured film was 250 μm, and then dried at 100° C. for 30 minutes to form a film, thereby preparing a semi-cured film of composition 1. The prepared semi-cured film was heated at 180° C. for 4 hours to prepare a 250 μm thick cured film of composition 1.

[0571] Using this evaluation sample, the volume content ratio of the filler in the film, the thermal conductivity, elastic modulus, shear adhesive strength, shear strain, and thermal cycle reliability of the film were evaluated.

[0572] <Examples 2 to 64 and Comparative Examples 1 to 3>

[0573] The same operations and evaluations as in Example 1 were performed using the compositions shown in Tables 3 to 10. The evaluation results are summarized in Tables 11 to 18. It should be noted that, for ease of comparison, the evaluation results of Example 3 are recorded in Tables 12 to 15 and 17, and the evaluation results of Example 8 are recorded in Table 16. It should be noted that the contents of fluorine element in the compositions in Examples 1 to 7, Examples 11 to 21, Examples 30 to 64, and Comparative Examples 1 to 3 are as described in Tables 3, 4, and 6 to 10, and the contents of fluorine element in the films are as described in Tables 11, 12, and 14 to 18.

[0574] [Table 11]

[0575]

[0576] [Table 12]

[0577]

[0578] [Table 13]

[0579]

[0580] [Table 14]

[0581]

[0582] [Table 15]

[0583]

[0584] [Table 16]

[0585]

[0586] [Table 17]

[0587]

[0588] [Table 18]

[0589]

[0590] In Comparative Example 1, (r-1) was contained as an amine compound instead of (SC). Since (r-1) lacked flexibility, the elastic modulus of the film at -50°C was much higher than 200 MPa, and the shear strain at -50°C was also lower than 0.70. Therefore, the thermal cycle reliability of the film was poor.

[0591] Comparative Example 2 does not contain the (SC) compound, and the elastic modulus at -50°C is not in the range of 0.10 to 200 MPa, and the shear strain at -50°C is not in the range of 0.70 to 20. Therefore, the film has poor thermal cycle reliability.

[0592] Comparative Example 3 contains polyimide (PI-11) as the (SA) binder resin. Since polyimide (PI-11) lacks flexibility, the elastic modulus of the film at -50°C is significantly large, and the shear strain at -50°C is significantly small. Therefore, the thermal cycle reliability of the film is poor.

[0593] Explanation of symbols

[0594] 10. First support

[0595] 20 Second support

[0596] 30 membrane

[0597] 40 Base member

[0598] 50 Ceramic dielectric components

[0599] 60 membrane

[0600] 100A, 200A laminate.

Claims

1. A film comprising (SA) a binder resin and (SD) a thermally conductive filler, The (SD) thermally conductive filler includes (SD1) a first thermally conductive filler and (SD2) a second thermally conductive filler. The average primary particle size of the first thermally conductive filler (SD1) is 1.0 to 200 μm, The average primary particle size of the second thermally conductive filler (SD2) is 0.010 μm or more and less than 1.0 μm, The shear strain of the film at -50°C is 0.70 to 20, The thermal conductivity of the film at 25° C. is 0.10 to 5.0 W / (m·K). 2 . The film according to claim 1 , which has an elastic modulus at -50° C. of 0.10 to 200 MPa.

3. The film according to claim 1 or 2, which satisfies at least one of the following conditions (S1a), (S2a), (S3a), (S1b), (S2b) and (S3b), (S1a) The boron content in the film is 5.0 mass % or less (S2a) The phosphorus content in the film is 1,000 mass ppm or less (S3a) The total content of chlorine and bromine in the film is 1,000 mass ppm or less (S1b) The total content of ions containing the boron element in the film is 5.0 mass % or less (S2b) The total content of ions containing phosphorus in the film is 5,000 mass ppm or less (S3b) The total content of chloride ions and bromide ions in the film is 1,000 mass ppm or less.

4. The film according to claim 1 or 2, which satisfies at least one of the following conditions (S4a) and (S4b): (S4a) The content of platinum in the film is 1,000 mass ppm or less (S4b) The total content of ions containing the platinum element in the film is 5,000 mass ppm or less.

5. The film according to claim 1 or 2, which satisfies at least one of the following conditions (S5a) and (S5b): (S5a) The total content of the organosilane compound having 1 to 2 silicon atoms in the film is 1,000 mass ppm or less. (S5b) The total content of the cyclic organosilicon compound in the film is 1,000 mass ppm or less.

6. A film comprising (SA) a binder resin and (SD) a thermally conductive filler, The elastic modulus of the film at -50°C is 0.10 to 200 MPa, The thermal conductivity of the film at 25° C. is 0.10 to 5.0 W / (m·K). The film according to claim 6 , which has a shear strain of 0.70 to 20 at -50° C.

8. The film according to claim 6 or 7, which satisfies at least one of the following conditions (S1a), (S2a), (S3a), (S1b), (S2b) and (S3b), (S1a) The boron content in the film is 5.0 mass % or less (S2a) The phosphorus content in the film is 1,000 mass ppm or less (S3a) The total content of chlorine and bromine in the film is 1,000 mass ppm or less (S1b) The total content of ions containing the boron element in the film is 5.0 mass % or less (S2b) The total content of ions containing phosphorus in the film is 5,000 mass ppm or less (S3b) The total content of chloride ions and bromide ions in the film is 1,000 mass ppm or less.

9. The film according to claim 6 or 7, which satisfies at least one of the following conditions (S4a) and (S4b): (S4a) The content of platinum in the film is 1,000 mass ppm or less (S4b) The total content of ions containing the platinum element in the film is 5,000 mass ppm or less.

10. The film according to claim 6 or 7, which satisfies at least one of the following conditions (S5a) and (S5b): (S5a) The total content of the organosilane compound having 1 to 2 silicon atoms in the film is 1,000 mass ppm or less. (S5b) The total content of the cyclic organosilicon compound in the film is 1,000 mass ppm or less. 11 . The film according to claim 1 , wherein the (SA) binder resin contains (SA1) a resin including an organic silicon structure and / or a siloxane structure in a structural unit of the resin. 12 . The film according to claim 11 , wherein the content ratio of the aliphatic group in the total of the aliphatic group and the aromatic group bonded to the silicon atom in the organic silicon structure and / or the siloxane structure is 80 to 100 mol %.

13. The film according to claim 11, wherein the resin (SA1) includes a silicone structure and / or a siloxane structure in the structural unit of the resin and (SA1-1) includes a resin selected from the group consisting of an imide structure, an amide structure and a More than one resin in the azole structure.

14. The film according to claim 13, wherein the (SA1-1) contains a structural unit selected from the group consisting of an imide structure, an amide structure and One or more resins in the azole structure have one or more residues selected from the following (1) and (2), (1) A diamine residue, a diamine derivative residue, a bisaminophenol compound residue, or a bisaminophenol compound derivative residue containing an organosilicon structure and / or a siloxane structure (2) A tetracarboxylic acid residue, a tetracarboxylic acid derivative residue, a tricarboxylic acid residue, a tricarboxylic acid derivative residue, a dicarboxylic acid residue or a dicarboxylic acid derivative residue containing an organosilicon structure and / or a siloxane structure.

15. The film according to any one of claims 1, 2, 6 and 7, comprising a (SB) compound which is an epoxy compound or a compound having a structure derived from an epoxy compound, The (SB) compound contains one or more selected from (SB1) a compound having a structure containing an oxyalkylene group, (SB2) a compound having a structure containing at least two aromatic structures and having a structure containing an oxyalkylene group, and (SB3) a compound having a tertiary amine structure bonded to an arylene group and two divalent organic groups.

16. The film according to any one of claims 1, 2, 6 and 7, comprising a (SC) compound which is an amine compound or a compound having a structure derived from an amine compound, The (SC) compound contains (SC1) a compound having an organosilicon structure and / or a siloxane structure and having at least two alkylene groups bonded to a silicon atom in the organosilicon structure and / or the siloxane structure. 17 . The film according to claim 1 , which has an elastic modulus of 0.010 to 1.0 MPa at 25° C.

18. The film according to any one of claims 1, 2, 6 and 7, which is a cured product of the composition.

19. The film of any one of claims 1, 2, 6 and 7, which is used in an electrostatic chuck.

20. A laminated body comprising, in this order, a base member, the film according to any one of claims 1, 2, 6 and 7, and a ceramic dielectric member, The base member and the ceramic dielectric member have different thermal expansion coefficients. 21 . The laminate according to claim 20 , wherein a difference in thermal expansion coefficient between the base member and the ceramic dielectric member is 1.0 to 30 ppm / K.

22. A plasma processing apparatus comprising a plasma generation source and the laminated body according to claim 20.

23. A method for producing a laminate, comprising the steps of: disposing a base member, disposing the film according to any one of claims 1, 2, 6 and 7, and disposing a ceramic dielectric member.

Citation Information

Patent Citations

  • Heat dissipating member and method of manufacturing the same

    JP2011151280A

  • Part for semiconductor manufacturing device, and method for manufacturing the same

    JP2014207374A